GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2018)
A dataset containing 1038516773 species occurrences available in GBIF matching the query: All data. The dataset includes 1038516773 records from 20000 constituent datasets: 197469 records from UMMZ Herpetology Collection. 355 records from Abundance of Polychaeta species in surface sediments of the east Greenland continental slope (75° N section). 6 records from Two new species of Guyruita Guadanucci et al., 2007 (Araneae, Theraphosidae) from Brazil. 10 records from New species of Graphocaecilius Enderlein (Psocodea: ‘ Psocoptera’: Lachesillidae) from Colombia. 2 records from A new species of Polyipnus (Stomiiformes: Sternoptychidae) from the Western South Pacific. 892 records from (UTC) University of Tennessee Mammals Collection. 21695 records from Birds Specimens. 58 records from Schulgelände Kranich-Gymnasium (Salzgitter). 6 records from Contributions to the study of Idiocerinae (Homoptera: Auchenorrhyncha: Cicadellidae) of Central Asia with notes on synonymy. 125 records from (Table 2) Absolute abundance of Contusotruncana contusa in DSDP Hole 74-525A. 1 records from A revision of the Anthaxia (Anthaxia) midas Kiesenwetter, 1857 species-group (Coleoptera: Buprestidae: Anthaxiini). 86 records from Fliegenhaupt Marksuhl. 56 records from Planktic foraminifera abundance of Hole 23-227. 92 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 18805 records from DMNS Mammal Collection (Arctos). 2199 records from Back from the Brink vascular plant species abundance and distribution for Great Britain for the period 2002-2009. 43 records from (Table 9) Biological parameters of stratigraphic horizons in Core AMK7-734 according to foraminifera. 110 records from Occurrence of mammalia relicts at site Rejtek 1. 1 records from A new species of the genus Pachytriton (Caudata: Salamandridae) from Hunan and Guangxi, southeastern China. 226 records from (Table 2) Stable oxygen and carbon data, and relative abundances of selected planktonic foraminiferal species in the surface sediment samples retrieved during the SO-189 cruise off W Sumatra. 2281 records from Relative abunances of benthic foraminifera in Late Oligocene to Miocene sediments of ODP Hole 121-757B from the southeastern Indian Ocean (Appendix Table 1). 6 records from Culicoides Latreille biting midges (Diptera: Ceratopogonidae) of the Dongzhaigang mangrove forest, Hainan Province, China. 881 records from Relative abundance of adult opstracoda shells of surface sediment samples from the Persian Gulf (Table 1b). 82 records from Taxonomic review of the ladybird genus Sticholotis from China (Coleoptera: Coccinellidae). 785 records from Colección de Mamíferos Marinos del Centro Nacional Patagónico. 1519 records from IBF Monitoring of Fungi. 5 records from Cryptic species among bumblebee mimics: an unrecognized Hemaris hawkmoth (Lepidoptera: Sphingidae) in eastern North America. 2242 records from (Table 3) Distribution of planktonic foraminifera in the early Cretaceous and early Eocene to late Oligocene sections of ODP Hole 149-897C. 27 records from Benthic foraminifera and algae abundance of Hole 81-553. 11 records from A new species of Decomia Poppius from Laos and Thailand, with an annotated checklist and keys to genera and species of tribe Decomiini from Indochina (Hemiptera: Heteroptera: Miridae: Phylinae). 1809 records from BenthosChukchiFN762_1976_Falk5. 883 records from Nannofossil abundance of Hole 15-154A. 43 records from Macrofauna abundance in surface sediment sampled during cruise DI237. 119 records from Programme de valorisation des zones humides chassées - volet Amphibiens. 3018 records from Caracterización de flora, edafofauna epígea, anfibios y aves del Complejo de Páramos Pisba, Boyacá. 1003 records from Fig. 4. Pollen record of profile SAO1 (Analyst: J. Hahne). 10170 records from Données de la collection d'ichtyologie du MNHN (GICIM). 104 records from Catalog of the Paramacronychiinae of China (Diptera: Sarcophagidae). 1 records from A new species of Ascidiacea (Herdmania andamanensis sp. nov.) from Andaman and Nicobar Islands, India. 53 records from Données 2017 de l'Observatoire de la Biodiversité des Forêts. 240 records from Knechtweide (Kohlfurth). 18 records from Benthic macrofauna abundance of sediment core 12930-073. 4 records from Description of Rhamma dawkinsi (Lepidoptera: Lycaenidae) a new mountain butterfly from Colombia. 582 records from Stable isotope data and sedimentology of core SO42-74KL. 89 records from Meniscus Midges (Dixidae) of Ireland. 73 records from Revision Of The Spider Genus Neoanagraphis (Araneae, Liocranidae). 171 records from Alien Species in Poland - Animals. 279 records from Large protozoan and small metazoan abundance measured on concentrated water bottle samples at station PS65/591-11. 1 records from A new deep-sea species of the caridean genus Bresilia Calman, 1896 (Crustacea: Decapoda: Bresiliidae) from Sagami Bay, central Japan. 3 records from Description of a new species of the genus Agamura Blanford, 1874 (Squamata: Gekkonidae) from southern Iran. 224 records from Natura 2000 PnrL. 11030 records from Census of the species of Benin. Data mobilized in the framework of JRS Benin project and funded by JRS Biodiversity Foundation. 3 records from Aradidae from Vietnam V. Bifurcatoaptera, a new genus of apterous Carventinae (Hemiptera: Heteroptera: Aradidae) from Vietnam. 973 records from Zambian Bat Collections Worldwide. 8 records from The genus Zelurus Hahn, 1826, in Brazilian caves: description of new species and comments on the potential distribution of the genus in South America. 466 records from PSU-Seagrass Collection. 1196 records from Entomological collection of the National Museum. 30917 records from Vascular plants of south-central China. 206 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/041-2. 144 records from BIRDRACE Punkbirder Helgoland. 1 records from Miriapodi di alcune grotte della Campania. 277 records from Inventario de gasterópodos terrestres y dulceacuícolas del área focal de Ixcan, Chiapas. 53 records from (Table 2) Benthic foraminifers at DSDP Hole 72-515A. 8 records from More cautionary tales: family, generic and species synonymies of recently published taxa of ghost and mud shrimps (Decapoda: Axiidea and Gebiidea). 318 records from Nannofossil abundance of Hole 4-29. 2498 records from Helmintos parásitos de peces del sureste de México. 383 records from Inventario de Peces del SFF Isla Malpelo, Proyecto Colombia Bio. 61 records from Naturpark Kottenforst-Ville 15.6.09. 2 records from Cnemaspis rajakarunai sp. nov., a rock dwelling day-gecko (Sauria: Gekkonidae: Cnemaspis) from Salgala, an unprotected lowland rainforest in Sri Lanka. 11 records from A new species of Neobathyclupea from the northern Indian Ocean with comments on N. malayana (Teleostei, Perciformes, Bathyclupeidae). 418 records from Radiolaria assemblage in sediment core GIK23259-2. 268 records from Range table from benthic foraminifers in ODP Hole 159-959A. 63 records from Total foraminifera counts of multinet M21/4_MSN706. 31 records from Pastinachus solocirostris sp. nov., a new species of Stingray (Elasmobranchii: Myliobatiformes) from the Indo-Malay Archipelago.. 294 records from Distribution of calcareous foraminifers in sediment core Well 6407/9-3. 173 records from FFH-Gebiet Klosterwasser/Burkau. 16 records from A new species of poison-dart frog (Anura: Dendrobatidae) from Manu province, Amazon region of southeastern Peru, with notes on its natural history, bioacoustics, phylogenetics, and recommended conservation status. 748 records from (App 10) Relative contents of indicator species of planktonic foraminifera in sediments from Core S-17666. 353 records from Données naturalistes de Hubert GUIMIER. 1728 records from Collection rousset -1947-2013. 1860 records from Données naturalistes de Hervé BOUYON. 10 records from Ten new species of the spider genus Pholcus Walckenaer, 1805 (Araneae, Pholcidae) from Southeast Asia. 399 records from (Table 2) Distribution of recurrent planktonic foraminifera at DSDP Hole 75-530A. 386 records from Thistle Heads and Ermerged Insects. 177 records from Review of some species groups of the genus Oospila Warren, with descriptions of nine new species (Lepidoptera: Geometridae: Geometrinae). 108 records from Total foraminifera counts of multinet M21/2_MSN629. 154 records from Planktic foraminifera assemblage in sediment core GIK23065-2. 1 records from Schulman's Neotropical Adelobotrys database. 1 records from An interesting new genus of Berothinae (Neuroptera: Berothidae) from the early Eocene Green River Formation, Colorado. 365 records from Colección Herpetológica de la Patagonia. 1 records from Description of a new species of genus Trachischium with a redescription of Trachischium fuscum (Serpentes: Colubridae: Natricinae). 4 records from On Plesionika persica (Kemp, 1925) and P. reflexa Chace, 1985 (Crustacea: Decapoda: Pandalidae) from India. 55 records from Vegetationsmatrix schorfheide alb 2008 durchgang2. 152 records from Total foraminifera counts of multinet POS247/2_MSN1372. 2 records from Dinoflagellate abundance of Hole 85-572C. 1 records from Earthworm species in various land use systems in the Campos Gerais region of Lapa, Paraná, Brazil. 25 records from Forest Spiders of South East Asia With a revision of the sac and ground spiders (Araneae: Clubionidae, Corinnidae, Liocranidae, Gnaphosidae, Prodidomidae and Trochanterriidae).. 771 records from Pseudoscorpiones Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 21 records from Description of a new species of Euptychiina (Lepidoptera: Nymphalidae: Satyrinae) from South America. 9054 records from Highland bird data 2002 - 2003 - non-breeding records. 9349 records from Harriet Irving Botanical Gardens (HIBG). 130 records from ABC_Ndangopuma_hills_eventdata_25_11_2005. 99 records from Total foraminifera counts from M35/1_MSN1061. 88 records from Plasm bearing foraminifera counts of multinet M21/2_MSN627. 4158 records from RNF - Données du Parc Naturel Régional du Vercors. 45 records from Crustacea specimens of Kuroshio Biological Research Foundation. 1941 records from (Table 19) Ranges of benthic foraminifers from the late Neogene through the Pleistocene in ODP Hole 115-707A. 3078 records from Insectes Hyménoptères Scollidés de France. 47 records from Taxonomic status of the Guadalupe Darter, Percina apristis (Teleostei: Percidae).. 3 records from First description of the male of the type species Meotipa picturata Simon, 1895 and description of a new Meotipa species (Araneae, Theridiidae) from India. 4717 records from Weddell Sea macrozoobenthos EASIZ I. 1345 records from Distribution of planktic foraminifera in sediment core GIK23415-9. 916 records from IOW Natural History & Archaeological Society Marine Records. 17 records from A new species of Leptolalax (Anura: Megophryidae) from northern Vietnam. 7527 records from Fauna y flora en áreas con cultivos de palma de aceite en el norte y oriente de Colombia. 71 records from Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010. 12 records from Cyanobacteria, phototrophic and heterotrophic pico-nanoplankton at station TT007_10-CTD124. 2528 records from Communauté_de_communes_Asse_Bléone_Verdon_2017_12_18. 14 records from Occurrence of mammalia relicts at site Climauti II. 361 records from Phytoplankton abundance measured on water bottle samples at station PS65/545-1. 800 records from (Table 9) Distribution of Neogene planktonic foraminifers in sediments of ODP Hole 115-711A. 3537 records from ATCC Bacteria Collection Catalog. 2436 records from Diet results from Adelie penguins at Bechervaise Island and Whitney Point, 2012/13. 156 records from SNH Invertebrate Site Condition Monitoring 2013/14: Earlshall Muir SSSI. 5 records from A New Southern Caribbean Species of Angel Shark (Chondrichthyes, Squaliformes, Squatinidae), Including Phylogeny and Tempo of Diversification of American Species. 1 records from A new Camponotus from Madagascar and a small collection of ants from Mauritius.. 6 records from (Table 1) Nesting characteristics of greater snow geese (Chen caerulescens atlanticus) on Bylot Island between 1995-2005. 12 records from Nano and microzooplankton abundance and biomass at station NBP97-01-01-10. 157 records from Planktic foraminifera counts at CTD station PS55/078-1. 355 records from (Table 2) Species density and composition of an inshore and offshore station in Kongsfjord, Svalbard. 4 records from Determinación de la clase Reptilia presente en el corregimiento de Juanchaco, Valle del Cauca, Colombia para el mes de Septiembre de 2017. 11 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 30-63 µm fraction. 79 records from Birdrace-Bielefinken-Bielefeld. 107 records from Müritz-Nationalpark. 125 records from Range table from ostracoda in ODP Hole 143-866B. 65 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-2. 913 records from Phytoplankton abundance in surface water in October 1997, Pisco, Peru. 6004 records from Colección Limnológica Universidad de Antioquia. 3 records from First record of Cephenniitae in the Bismarck Archipelago, Papua New Guinea, with description of new species of Cephennodes and Cephennomicrus of Mussau and Manus Islands (Coleoptera, Staphylinidae, Scydmaeninae). 146 records from Birdrace-Wannacks_Topti(c)ker-Lübeck. 272 records from Wald am Schloss Wittgenstein Bad Laasphe. 659 records from Museo Provincial de Ciencias Naturales “Dr. Ángel Gallardo”, Rosario, Argentina - Colección Peces (MG-ZV-P). 180614 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 3529 records from A dataset from bottom trawl survey around Taiwan. 35 records from Phytoplankton abundance in surface water in 2003, Ancon, Peru. 3 records from Metrocoris sikkimensis sp. nov. (Hemiptera: Heteroptera: Gerridae) from northeastern India, with a key to species of the compar group occurring in India. 9 records from The Maugean Skate, Zearaja maugeana sp. nov. (Rajiformes: Rajidae) - a micro-endemic, Gondwanan relict from Tasmanian estuaries.. 41 records from Phytoplankton abundance at station Sechin_2003-10-03_2, Casma, Peru. 3 records from Two new species of stargazers of the genus Uranoscopus (Teleostei: Uranoscopidae) from the western Pacific Ocean. 105 records from Abundance of macrobenthos organisms in the northern Wadden Sea in 2008. 746 records from Données naturalistes de François BRETON. 11 records from Rare And New For The Fauna Of The Russian Far East Spiders (Aranei). 20 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2004. 2 records from A new species of Lepidodactylus (Reptilia: Squamata: Gekkonidae) from the Kei Islands, Maluku, Indonesia. 26728 records from Museu Paraense Emílio Goeldi - Ophidia Collection. 210 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/108-3. 4 records from Zwei neue Arten der Oribatiden-Gattung Nanhermannia. 5264 records from (Table T1) Plankontic foraminifera stratigraphy of ODP Site 184-1143. 14 records from (Table 4b) Biomass of Emiliania huxleyi and its role in total biomass of phytoplankton along the section from the Pribilofs Islands to the Nunivak Island on 24-25 August 2001. 30008 records from Lepidoptera specimen database of Japan. 308173 records from DFO Maritimes Research Vessel Trawl Surveys Fish Observations. 2499 records from Leicestershire and Rutland Reptile Records to 2011. 33 records from Smear slide analysis on sediment core GeoB4214-1. 43 records from Assemblage of total living benthic foraminifera in sediment core SO129_MC-14. 1614 records from Culture Collection of Algae. 28545 records from Collection Vermes - ZMB. 130 records from BIRDRACE - The famous Grouse feat. The James. 374 records from Planktic foraminifera abundance of Hole 68-503B. 63 records from Distribution of meiofauna in surface sediments of the Iberian deep sea basin (Table 3). 45 records from Visual Plants (144.41.33.158) - Plants from the Kakamega Forest, Kenya; Helmut Dalitz. 26 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 µm. 18243 records from Distribution of planktic foraminifera in surface sediments of the Atlantic Ocean (ATL947). 552 records from Phytoplankton abundance in surface water in August 1997, Pisco, Peru. 370 records from Recursos hidrobiológicos de sistemas cársticos en el municipio de El Peñón, Santander - Proyecto Colombia BIO. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-13-4. 5 records from Three new country records from the genus Limnephilus Leach, 1815 (Trichoptera: Limnephilidae) from the Republic of Kosovo. 144 records from Diet, Tidal and Vertical Variations of Phytoplankton and Its Environment in Frobisher Bay, Canada, 1980 and 1981. 4 records from A new species of Creagrutus (Characidae: Stevardiinae) from the upper Río Magdalena, Colombia. 31 records from Taxonomic changes of some neotropical species of Arctiini Leach (Lepidoptera: Erebidae: Arctiinae). 265 records from Coarse fraction analysis and texture of biogenous sands from Josephine Seamount surface samples (Table 2). 52 records from Occurrence of mammalia relicts at site Goyet Cave 3. 592 records from (Table 2) Raw counts of planktonic foraminiferal species and varieties from the sediment surface samples from the South China Sea. 18 records from Schulgarten der Gesamtschule Am Heidberg. 22 records from Coccolith counts of multinet SO119_MSN1272. 2789 records from Museu Paraense Emílio Goeldi - Opiliones Collection. 1215 records from (Table 1) Distribution of planktonic foraminifera from samples spanning the Cretaceous-Tertiary boundary at ODP Hole 207-1259C. 153 records from Benthic meiofauna abundance in surface sediment of core PLG93_BCORE1. 480 records from (Tab. 6) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 41-370, Deep Basin West off Morocco. 70 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 21 records from Riedkanal Bötzingen. 7 records from One new species and one newly recorded species of Cyllodes Erichson from China (Coleoptera: Nitidulidae: Nitidulinae). 20 records from Planktic foraminifera abundance of Hole 19-185. 64 records from (Table T10) Calcareous nannofossil stratigraphy of ODP Hole 198-1212A. 1030501 records from Dragonfly records from the British Dragonfly Society's Dragonfly Recording Network for the period up to 2014. 19021 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) planctónicas más frecuentes en el Golfo de California. 2154 records from DBG Physaria bellii Demographic Monitoring. 22 records from A revision of the genus Disparalona (Cladocera, Chydorinae) in South America. 331 records from (Table IIa) Planktic foraminifera abundances in the latest Cretaceous sample interval of the Ben Gurion Section, Israel. 2140 records from Captive Primate Specimens of Japan Monkey Centre. 20 records from Size fractioned abundances and carbon biomasses of heterotrophic protists at station NIOP-B1_276-1. 61 records from Inventario de vertebrados nativos en las islas Guadalupe, San Benito, Natividad, Asunción, San Roque, Isabel, Marietas, Socorro, Banco Chinchorro y Arrecife Alacranes. 18 records from The genus Salfacarus (Acari: Opilioacarida) in Madagascar. 35 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/091-4. 36 records from Potamotrygon rex, a new species of Neotropical freshwater stingray (Chondrichthyes: Potamotrygonidae) from the middle and upper rio Tocantins, Brazil, closely allied to Potamotrygon henlei (Castelnau, 1855). 193 records from Planktic foraminifera abundance of Hole 94-610. 4621 records from Códigos de barras de la vida en peces y zooplancton de México. 7 records from The publication of primary biological events in the international GBIF (Global Biodiversity Information Facility) network: A case study with a small dataset of field collected occurrence samples of Buriti palms (Mauritia flexuosa).. 62324 records from Herbarium Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 69 records from (Table 5) Abundance of selected helicoliths at DSDP Site 82-563 in the North Atlantic. 4 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-1998-IR50. 5 records from Loricifera - SMF. 667 records from Antarctic Krill occurrence data from Discovery expeditions. 13 records from Rhaphium (Diptera: Dolichopodidae: Rhaphiinae) from China with six new species. 264 records from (Table 4) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-847B. 47 records from Updated checklist of Balearic leaf beetles (Coleoptera: Chrysomelidae). 480819 records from KTP Ring Data. 48 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1197. 14 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT012_3-CTD4. 7582 records from Tropical epiphyte diversity under human impact ? Comparing primary forests, secondary forests, and forest fragments in Ecuador - Otonga. 24 records from RNF - Données de la Réserve Naturelle du Marais de Lavours. 5 records from Description of two new species of the genus Automate De Man, 1888 (Crustacea: Decapoda: Caridea) from the South China Sea. 218 records from Revision of the Ephippiochthonius complex in the Iberian Peninsula, Balearic Islands and Macaronesia, with proposed changes to the status of the Chthonius subgenera (Pseudoscorpiones, Chthoniidae). 2 records from A new ant species of the Leptogenys sulcinodagroup (Hymenoptera: Formicidae) from Saudi Arabia. 1477 records from Inventaire des espèces végétales productives dans les Systèmes Agro-forestiers aux alentours de la Forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 207 records from BioAcoustica: Wildlife Sounds Database. 140 records from (Table 2) Occurrence of upper Maestrichtian to Eocene benthic foraminifers in ODP Hole 121-753A. 1824 records from TransForest vegetation data. 252 records from Systematics, distribution and biology of the Australian ' micro-flea' wasps, Baeus spp. (Hymenoptera: Scelionidae): parasitoids of spider eggs.. 201 records from Biodiversity of springs and rock seepages 2003. 127 records from Microzooplankton abundance measured on water bottle samples at station PS65/466-2. 1268 records from Actualización de la base de datos de crustáceos y registro de datos de peces del pacífico mexicano de la Colección Biológica de la Secretaría de Marina. 101 records from Correction of existing generic and species concepts in Platyceroidini (Coleoptera: Lucanidae: Lucaninae) and the description of four new species of Platyceroides Benesh. 1 records from Protozoa ZMK. 1 records from A new riparian Mantidactylus (Brygoomantis) frog from the Tsaratanana and Manongarivo Massifs in northern Madagascar. 521 records from Schanzenanlage Bergham. 140 records from Planktic foraminifera abundance of Hole 37-332. 2 records from A new limestone-dwelling leaf-toed gecko (Gekkonidae: Dixonius) from Khao Sam Roi Yot massif, peninsular Thailand. 10 records from Review of the cave cricket genus Tamdaotettix Gorochov with a new species and some new descriptions (Orthoptera: Rhaphidophoridae, Aemodogryllinae). 2205 records from (Table 2) Calcareous nannofossil distribution in the Upper Cretaceous of ODP Hole 120-748C. 4 records from Distribution of Quinqueloculina sp. in sediment core 13200-025. 6746 records from Crustacean specimens of Kitakyushu Museum of Natural History & Human History. 98 records from Total foraminifera counts of multinet POS231/3_MSN1332. 75 records from The interstitial subsoil fauna of the lower beach level at Sarso Beach, Red Sea (Table 4). 234 records from Données Phesulma borbonica du Parc national de La Réunion - COBE03. 122 records from Southern distributional limits of Meliponini bees (Hymenoptera, Apidae) in the Neotropics: taxonomic notes and distribution of Plebeia droryana and P. emerinoides in Argentina. 909 records from Phytoplankton abundance and species composition in the Tyrrhenian Sea in November 1981. 123 records from Abundance of dead benthic foraminifera in sediment core CD86_06_BC5. 444 records from Marsabit Ecosystem Inventory Surveys 2014. 3 records from Dactylogyrids (Monogenea) parasitic on marine fish from Peru including the description of a new species of Haliotrema Johnston & Tiegs, 1922 and two new species of Parancylodiscoides Caballero & C. & Bravo-Hollis, 1961. 7 records from On the taxonomic status of the European Scolelepis (Scolelepis) squamata (Polychaeta: Spionidae), with description of a new species from southern Europe. 561 records from Colección de Vertebrados (naturalizados y en fluido) del Departamento de Zoología de la Facultad de Biología de la Universidad de Sevilla. 2 records from Two more new species of Hemiphyllodactylus Bleeker (Squamata: Gekkonidae) from the Shan Hills of eastern Myanmar (Burma). 1052 records from Nannofossil abundance of Hole 37-334. 6 records from New ants (Hymenoptera: Formicidae) from Micronesia. 4 records from A new anchialine species of Naushonia (Decapoda: Gebiidea: Laomediidae) from the Bahamas. 59 records from Schulgelände SGD/Viersen. 42 records from Flies from L.A., The Sequel: A further twelve new species of Megaselia (Diptera: Phoridae) from the BioSCAN Project in Los Angeles (California, USA). 75 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 1306 records from Flora genérica de las gramíneas del estado de Tlaxcala. 3 records from A new genus of Hemerobiidae (Neuroptera) from Baltic amber, with a critical review of the Cenozoic Megalomus - like taxa and remarks on the wing venation variability of the family. 1 records from Zur Kenntnis der Lithobiiden. 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 322 records from Nannofossil abundance of Hole 84-570. 2 records from A new species of Paraleptophlebia Lestage, 1917 (Ephemeroptera: Leptophlebiidae) and a re-description of adults for Paraleptophlebia westoni Imanishi, 1937 with the first description of the larva, from the Russian Far East. 2 records from Phasmarhabditis bonaquaense n. sp. (Nematoda: Rhabditidae), a new slug-parasitic nematode from the Czech Republic. 1341 records from Late Albian Col de Palluel (SE France, Niveau Breistroffer): range chart in percentages of calcareous nannofossils. 53 records from Leopard and Weddell seal program 1999/2002. 4309 records from Données naturalistes de Ségolène FAUSTEN. 62 records from Distribución, abundancia y efectos nocivos de tres especies de plantas invasoras. 3 records from Drepanosticta adenani sp. nov., from the Lanjak Entimau Wildlife Sanctuary in Sarawak (Odonata: Zygoptera: Platystictidae). 22167 records from Natural History Museum Maastricht (NL) - Herbarium. 172 records from Foraminifera abundance of sediment core MD81-LC07. 103 records from Invertebrate collections. 403 records from Range table from benthic foraminifers in ODP Hole 181-1119C. 2 records from Microlepidogaster negomata, a new hypoptopomatine catfish (Loricariidae: Hypoptopomatinae) from Rio São Francisco basin, southeastern Brazil. 17114 records from Collection of Coleoptera. 74 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 1 records from Karpfenteich, Klasse 6d. 6 records from Range table from planktonic foraminifers in ODP Hole 145-883C. 64 records from Review of the genus Prays Hübner, 1825 (Lepidoptera: Praydidae) from China, with descriptions of twelve new species. 179 records from Total foraminifera counts of multinet SO117_MSN1244. 30501 records from Canada Maritimes Regional Cetacean Sightings (OBIS Canada). 8956 records from Formación de una base de datos de la biodiversidad de fauna marina y costera en el Golfo de California. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 15 records from Monitoreo de Murciélagos en la Etapa de Ejecución de las Obras de Ampliación del EPF Floreña, Yopal, Casanare. 9 records from Two new species of Garreta Janssens, 1940 (Coleoptera: Scarabaeidae: Scarabaeinae) from Southern Africa. 1 records from A new species of Silba (Diptera; Lonchaeidae) associated with figs. 3435 records from Benthos Chirnov Basin 1986 and 2002. 6 records from (Table 5) Paleotemperature estimates for DSDP Hole 81-552A. 869147 records from Queensland Museum provider for OZCAM. 71 records from Range table from planktonic foraminifers in ODP Hole 182-1133C. 69 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1379. 192 records from (Table 3) Absolute concentrations and raw counts of seven genera of dinoflagellate in ODP Site 170-1039. 70 records from Coccoliths in sediment core GIK23065-3. 708 records from EDP Baixo Sabor: Herpetology – Baseline Studies [2009]. 1 records from Molche in Ruschwedel. 251 records from Review of the Madagascan Orphninae (Coleoptera: Scarabaeidae) with a revision of the genus Triodontus Westwood. 6 records from Two new records and one new species of the genus Apelaunothrips from China (Thysanoptera: Phlaeothripidae). 96 records from Plasm bearing foraminifera counts of multinet M21/1_MSN620. 1004 records from Actualización de la base de datos de la Colección nacional mexicana de cultivos microbianos. 448 records from (Table 4) Distribution of the large, many-chambered Globigerinelloides species in the Cismon core. 44 records from New and poorly known Holarctic species of Boletina Staeger, 1840 (Diptera, Mycetophilidae). 107 records from Range table from benthic foraminifers in ODP Hole 146-889B. 10 records from Three new genera and three new species of Nearctic Lasiopteridi (Diptera: Cecidomyiidae: Cecidomyiinae) from Asteraceae and Caprifoliaceae, and the tribe Rhopalomyiini subsumed under Oligotrophini. 701 records from Données naturalistes d'Arnaud LE NEVÉ. 2147 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 20416 records from Zomerganzen - Summering geese management and population counts in Flanders, Belgium. 12 records from Analyses of the recent components of sediment core PS1219-1. 717 records from Redland City Council Citizen Science Portal. 44802 records from Insect collection of Biodiversity Center of Japan, Ministry of the Environment. 17 records from New species, new records, and new collection data of Rhyacophila from China (Trichoptera: Rhyacophilidae). 239 records from Caracterización de algas y comunidad íctica de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 311 records from HBRG Invasive Non-native Plants Dataset. 6 records from Pushing the limits - two new species of Pteromalus (Hymenoptera, Chalcidoidea, Pteromalidae) from Central Europe with remarkable morphology. 166 records from Steinbruch Mainz-Weisenau, 3. Jahr. 1834 records from Museu Paraense Emílio Goeldi - Carcinológica Collection. 15 records from Additions to the ichthyofauna of the Tristan da Cunha Group, South Atlantic Ocean.. 3251 records from Inventario florístico de la Sierra de Huautla, Morelos. 806 records from Pollen profile V and Ausfluss at Krumbach, Germany. 622 records from Inventario de sanguijuelas (Annelida: Clitellata Hirudinea) de México, con énfasis en las especies del centro de México. 229 records from Queen Charlotte Sound / Tōtaranui and Tory Channel / Kura Te Au (HS51) Hydrographic Survey Marine Mammal Observations. 5 records from Society Islands beach bum black flies (Diptera: Simuliidae). 965 records from Nannofossil abundance of Hole 75-532. 62 records from Données de Mammifères marins en Polynésie française issues du South Pacific Whale Research Consortium. 1 records from A new species of Andinobates (Anura: Dendrobatidae) from the Urabá region of Colombia. 15 records from Microzooplankton abundance and biomass at station NBP97-08-29-1. 2726 records from Computarización de material complementario en la Colección Regional de Invertebrados del Pacífico mexicano, Instituto de Ciencias del Mar y Limnología, Unidad Académica Mazatlán, UNAM. 36 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-51, 30-63 µm fraction. 163 records from Base de datos de fauna batial, abisopelágica y abisal del Golfo de México. 81329 records from natagora-earlybirds. 32 records from Abyssal fauna of the UK-1 polymetallic nodule exploration claim, Clarion-Clipperton Zone, central Pacific Ocean: Echinodermata. 9858 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-MUSCI. 18 records from Range table from planktonic foraminifers in ODP Hole 167-1010B. 6862 records from Hormigas del Museo de Entomología de la Universidad del Valle. 2 records from Macrocyrtus imomzodai Barševskis, 2016, a new synonym of Metapocyrtus (Orthocyrtus) orbiferoides Schultze, 1918 (Coleoptera: Curculionidae: Entiminae). 35 records from Reptiles Specimens of Akita Prefectural Museum. 339 records from UWIZM Snakes. 341 records from Electron Micrograph Database - Terrestrial and Limnetic Specimens. 5276 records from Biodiversidad de la Sierra Tarahumara. Lepidoptera: Mimallonoidea, Lasiocampoidea, Bombycoidea y Pyraloidea. 364 records from Nannofossil abundance of Hole 85-573. 10 records from Catalogue of Ampulicidae, Crabronidae and Sphecidae of Iran (Hymenoptera, Apoidea). 8 records from Abundance and carbon biomass of phytoplankton at station TT007_9-CTD113. 145 records from Biodiversity survey of Rugezi wetland, Year 2013. 1 records from Seven new species of Night Frogs (Anura, Nyctibatrachidae) from the Western Ghats Biodiversity Hotspot of India, with remarkably high diversity of diminutive forms. 449 records from Artsprosjekt Pyrenomycetes. 1577 records from (Table 2) Stratigraphic distribution of dinocyst taxa in ODP Hole 150-903A. 168 records from Assemblage of living benthic foraminifera in sediment core GeoB4916-4. 33 records from Microzooplankton abundance and biomass at station TT043_27-1. 1 records from Brachiopods Specimens of Akita Prefectural Museum. 58 records from Relative abundance of live benthic foraminifera of sediment core M5/2_98MC. 2421 records from Managing open habitats for species conservation: the role of wild ungulate grazing, small-scale disturbances, and scale - Tanacetum vulgare dominated forb vegetation. 11086 records from (Table 2) Distribution of late Miocene to Pleistocene calcareous nannofossils in ODP Hole 105-646B. 4 records from A new Aceria species (Acari: Prostigmata: Eriophyoidea) from Minuartia frutescens (Caryophyllaceae) in Hungary. 17 records from (Table 2.2.1.1) Abundance of sympagic meiofauna of sea-ice core IO-5. 7791 records from Base de datos de las gramíneas (Poaceae) del noreste de México. 176 records from Renaturierung Werse (Innenbereich Beckum). 23 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/390-1a. 54073 records from FUEL - Herbário da Universidade Estadual de Londrina. 292 records from Atlantic Forestry Centre Insect Reference Collection. 4036 records from Inventario de larvas de peces en la región sur del Golfo de California (GAP 81, 85 y 86) y en el Pacífico Tropical Mexicano (GAP 88-91). 1 records from Eine Milbendiagnose aus dem Nachlass Dr. Josef Schweizer. 240635 records from Dataflos. 37 records from (Supplement Table 3) Percentage cover abundance of plants recorded at the Fell-field Site on Disko Island. 11454 records from Dragonfly (Odonata) species records up to 1997 held by Leicestershire Environmental Resources Centre. 175 records from The cicada genus Procollina Metcalf, 1952 (Hemiptera: Cicadidae): redescription including fourteen new species, with a key to the species of the subtribe Dazina Kato, 1932 rev. stat., the description of the Aragualnini n. tribe, and one new combination. 35 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 63-125 µm fraction. 20191 records from Seabirds in Norway - Estimated population sizes. 80 records from Range table from planktonic foraminifers in ODP Hole 139-855A. 1470 records from Institut Menorquí d'Estudis. Herbarium Generale Minoricae: HGM. 247 records from Abundance of large foraminifera in cores from transect NOG-01B, IODP Expedition 325. 2136 records from (Table 1) Relative abundance of planktic foraminifera in Maastrichtian sediments of DSDP Hole 74-525A from the Walvis Ridge, South Atlantic Ocean. 25 records from Inventario de Murciélagos Buenos Aires, Tauramena, Casanare. 8410 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 3005 records from Colección Entomológica CDMB. 1 records from A new species of the subgenus Troginus Mulsant et Rey 1878 (Coleoptera: Staphylinidae: Oxytelinae: Carpelimus) from Borneo. 196 records from (Fig. 10) Distribution of dinoflagellate cysts in Early Cretaceous sediments of DSDP Hole 41-367 in the North Atlantic. 16933 records from Lepidoptera (Specimens NRM). 327 records from Colección nacional de palmas de Colombia - JBQ. 993 records from ROC RSPB Farmland Species Survey Dataset. 3269 records from Relative abundance of radiolaria in surface sediments. 205 records from Wild boar sightings held by Andy Riches. 822 records from Las comunidades de myxomicetes de selva baja caducifolia. 182049 records from Florida Keys Reef Visual Census 1999. 108 records from (Fig. 5a) Limacina dissolution index of sediment core GeoB2205-4. 27810 records from Collection of saproxylic and xylobiont Beetles. 781 records from Composición florística y estructura de tres parcelas permanentes en diferentes estados sucesionales en transición de bosques húmedos tropicales con bosques secos tropicales del municipio de Lebrija, Santander (Primer censo). 110 records from Range table from planktonic foraminifers in ODP Hole 144-875C. 415 records from Caracterización de vegetación para el establecimiento de límites funcionales de humedales: Ciénaga de la Virgen, Ciénaga Zapatosa y Complejo Hato Corozal - Paz de Ariporo. 10 records from Occurrence of mammalia relicts at site Meiendorf. 22586 records from Tachinid Recording Scheme - GB and Ireland records. 36 records from Two new species of Isbrueckerichthys Derijst, 1996 (Siluriformes: Loricariidae) from the rio Paranapanema basin, Brazil.. 241 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto120-128. 4617 records from Données de type contact de Guadeloupe. 14568 records from Canadian Museum of Nature Palynology Collection. 97 records from Microzooplankton abundance measured on water bottle samples at station PS65/570-4. 261 records from Planktic foraminifera abundance of Hole 63-469. 1284 records from Données naturalistes de Thomas LORICH. 89 records from New records of Ichneumonidae (Hymenoptera) for the Italian fauna. 408 records from Planktic foraminifera abundance of Hole 23-220. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_5-CTD58. 130 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB07 in the euphotic zone of the Aegean Sea in spring 1997. Part 1 - diatoms. 36 records from Planktic foraminifera assemblage in sediment core GIK23243-2. 96 records from Range table from benthic foraminifers in ODP Hole 172-1060B. 2 records from Osteology and relationships of Libanopycnodus wenzi gen. et sp. nov. and Sigmapycnodus giganteus gen. et sp. nov. (Pycnodontiformes) from the Late Cretaceous of Lebanon. 55 records from Galls on Beech Trees in Hainich, 2008. 2039 records from Atlas des Poissons et Crustacés d'eau douce de Guadeloupe. 15 records from Three new species of Holoscolex (Clitellata, Glossoscolecidae) from the Gurupi Biological Reserve, last forest remnant of the Belém Endemism Area, Eastern Amazon. 154 records from Range table from planktonic foraminifers in ODP Hole 170-1041A. 1037 records from Evaluación del estado actual de las poblaciones silvestres de chigüiros (Hydrochoerus hydrochaeris) en los municipios de Paz de Ariporo y Hato Corozal, Casanare. 37 records from (Table 4) Principal component analysis, paleotemperatures and distribution of infaunal benthic foraminifera in Late Quaternary sediments of core BMR96GC21 in the southeast Indian Ocean. 659 records from (Table 1) Pleistocene planktonic foraminiferal assemblages at ODP Site 128-798. 31788 records from Observatoire de la Biodiversité des Jardins (OBJ). 129 records from Plasm bearing foraminifera counts of multinet M21/2_MSN657. 1 records from Arthropoden aus südostalpinen Höhlen.. 469 records from Nannofossil abundance of Hole 10-94. 118 records from Données de Mammifères marins dans les TAAF et autres territoires issues de la bibliographies. Compte cardobs 1007 (Trudelle). 1 records from Ctenophora ZMK. 9 records from Studies in Mexican Grasshoppers: A new species of Pedies Saussure (Acrididae: Melanoplinae) with comments on the unusual blue coloration on the abdomens of females and live specimen images for three other congenerics. 182 records from Late Albian Col de Palluel (SE France, Niveau Breistroffer): results from planktic foraminifera. 2290 records from Benthic foraminifera abundance of Hole 84-568, Part 1. 5 records from Macrochelid mites (Mesostigmata: Macrochelidae) from São Paulo state, Brazil, with description of a new species of Macrocheles. 82 records from The genus Leucophenga (Diptera, Drosophilidae), part VII: the subpollinosa species group from China, with morphological and molecular evidence. 6263 records from Range table from nannofossils in ODP Hole 164-994C. 6 records from Description of a new Episemion species (Cyprinodontiformes: Nothobranchiidae) from northern Gabon and southeastern Equatorial Guinea.. 648 records from Range table from planktonic foraminifers in ODP Hole 182-1127B. 23 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-962D. 535 records from Pollen analysis of sediment core GeoB6518-1. 9 records from Three new taxa of Noctuidae from China (Lepidoptera: Noctuidae). 494248 records from BLS Mapping Scheme dataset, 1750-2009. 11 records from Description of lithologic section units of IODP Hole 325-M0055A. 244 records from Quarrendorfer Landschaftsschutzgebiet. 168 records from Registros de quirópteros de tres localidades del caribe colombiano. 34 records from Revision of the New World species of the genus Dinotrema (Hymenoptera: Braconidae: Alysiinae). 53 records from Relative abundance of planktic foraminifera in sediment core K11. 7 records from Range table from benthic foraminifers in ODP Hole 139-856C. 10 records from Dryinidae and Embolemidae (Hymenoptera, Chrysidoidea) from Anijima, Ogasawara Islands, Japan. 324 records from Range table from planktonic foraminifers in ODP Hole 170-1039B. 29 records from BMHS Crustacean Collection. 30 records from Descriptions of four new species of Semia Matsumura (Hemiptera: Cicadidae: Psithyristriini) from Vietnam, with a key to the species of Semia. 37 records from Range table from planktonic foraminifers in ODP Hole 169-1036B. 697 records from (Appendix 6) Benthic foraminifera at termination I in sediment core PS1906-2 in the Greenland Sea. 49 records from Données naturalistes (Rhopalocères et Zygènes) de Bob WHITMARSH (indépendant). 196 records from Collection des mammifères d'Auvergne. 12 records from Pseudotibiozus Demange, 1970 - millipedes of the Eastern Arc Mountains, Tanzania (Diplopoda, Spirostreptida, Spirostreptidae). 1 records from Synthèse de la Répartition des populations de cerf élaphe en 2000 (réseau Ongulés sauvages ONCFS-FNC-FDC). 16469 records from Arbeitsgemeinschaft Heuschrecken Österreichs. 11 records from Données d'observation opportunistes collectées durant la campagne de prélèvements sédimentaires SHELL/CREOCEAN en Guyane française en 2013. Shell Exploration and Production France. 1422 records from Australian Institute of Marine Science (AIMS) - Lizard Island Reef Biodiversity Expedition, Queensland, Australia (2008 - 2009). 588 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 48 records from Morphologische Daten von Natrix. 118 records from Collection botanique Lamy de la Chapelle E. (BOUM). 1703 records from (Table 3) Ranges of benthic foraminifers from the late Eocene through the Oligocene in ODP Hole 115-707A. 875 records from Caracterización biológica de la ventana de biodiversidad Montes de María, Municipio de Colosó, Sucre, Colombia. 9 records from Key to the currently recognized species of Limnias Schrank, 1803 (Rotifera, Monogononta, Gnesiotrocha, Flosculariidae). 95 records from BIRDRACE accipiter hardcore birding. 89 records from Occurrence of mammalia relicts at site Spitzbubenhöhle. 2 records from Orbinia wui, a new species from China, with redescription of O. dicrochaeta Wu, 1962 (Annelida, Orbiniidae). 9 records from A new genus and species of entocytherid ostracod (Ostracoda: Entocytheridae) from the John Day River Basin of Oregon, U. S. A., with a key to genera of the subfamily Entocytherinae. 6065 records from LISU Herbario Angola. 4749 records from CNAC/Coleccion Nacional de Acaros. 2 records from Intraspecific variation in adult Uvitellina iraquensis Dronen, Ali & Al-Amura, 2013 (Cyclocoelidae: Haematotrephinae) from two collection sites of white-tailed lapwing, Vanellus leucurus (Lichtenstein) (Charadriiformes: Charadriidae), in Iraq. 229 records from Distribución y estructura poblacional de la tortuga de Berlandier, (Gopherus [=Xerobates] berlandieri) en México. 466 records from Nannofossil abundance of Hole 4-31. 628 records from hauterivian_echinoids_of_the_paris_basin. 145 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/092-3. 258 records from PeECE II - Pelagic Ecosystem CO2 Enrichment Study, Raunefjord, Bergen, Norway. 135 records from Waldi-Weiher. 4751 records from Composition of planktonic foraminifera species from 310 sediments samples during the last glacial maximum. 210 records from (Table 1) Distribution of foraminifera in the Miocene section of ODP Hole 133-815A. 470 records from Gewann Krampf (Heilbronn). 4 records from On new or poorly known Australian Filistatidae spiders (Araneae: Araneomorphae), including a study on the fine morphology of Wandella. 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 17 records from Benthic macrofauna abundance of sediment core 13201-002. 64 records from Distribution of less-numerous macro-endofauna in surface sediments at Fladen Ground stations, North Sea (Table 4). 320 records from (Table S1) Nannofossil abundances at DSDP Hole 86-577. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_1-CTD8. 607 records from Inventory of Bassila forest (North-Benin). 1029 records from Circumpolar Seabird Monitoring Plan. 406 records from Pollen profile from Muscotah Marsh B. 30 records from Hydroids of the BANZARE Antarctic expeditions 1929 - 1931. 48 records from Catch related distribution of Appendicularia at station M9_C near the Great Meteor Bank, Northeast Atlantic (Table 8). 718 records from Planktic foraminifera assemblage of sediment core ELT49.023-PC. 120 records from (Table 10) Occurrence of benthic foraminifera in ODP Hole 112-688E, Part II. 51 records from Visual Plants (144.41.33.158) - Private collection of Asta Napp-Zinn. 80 records from (Table 2) Relative abundances of shallow-water foraminifera in ODP Hole 133-821A. 3340 records from Palaeobiology collection, FAU Erlangen. 46 records from Phytoplankton counted on two fractions of surface sediment samples from stations B-5 to B-47. 30 records from Planktic foraminifera abundance of Hole 14-144. 8 records from Revision of Terellia amberboae group of species (Diptera: Tephritidae). 819 records from Inventaire National du Patrimoine Naturel : CBN de Midi-Pyrénées. 364 records from (Table 10) Distribution of coccoliths in Core AMK7-734 from the Tajura Rift. 7 records from Hemichordata collection of National Museum of Nature and Science. 2183 records from Abundance of organic-walled dinoflagellate cysts of sediment core GeoB3603-2. 4 records from Settling the name Diomedea exulans Linnaeus, 1758 for the Wandering Albatross by neotypification. 239 records from Données naturalistes de Pauline BALDUCCI. 1 records from Planktic foraminifera abundance of Hole 54-420A. 40135 records from DIBA-Parc del Montnegre i el Corredor. 22 records from Caracterización de la epifauna y macrobentos (0-800 m) de Isla Cayo Serranilla y Áreas aledañas: Equinodermos primera fase 2017 - Proyecto Colombia Bio. 4764 records from USGS ASC - Yukon Kuskokwim River Delta - Birds - 1992-2002. 223 records from Planktic foraminifera abundance of Hole 40-362A. 8 records from A new species of Polietina (Diptera: Muscidae) from South America, with an updated phylogeny of the genus and a review of species’ identity in GenBank. 21456 records from Muséum_de_Toulon_et_du_Var_2017_12_18. 3 records from Review of the genus Bythonia Oman 1936 with description of a new species and new record from Venezuela (Hemiptera, Cicadellidae, Iassinae). 17 records from Description of lithologic section units of IODP Hole 325-M0043A. 7 records from Grundwasserlebensraum im Englischen Garten (München). 1993 records from Inventario de macroalgas de Isla Guadalupe, México. 213 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE218. 52 records from Range table from planktonic foraminifers in ODP Hole 167-1010E. 10 records from A new species of the swimming crab genus, Laleonectes Manning & Chace, 1990 (Crustacea: Brachyura: Portunidae), from the western Indian Ocean. 9150 records from The Collection of Lichenicolous Fungi at the Botanische Staatssammlung München. 115 records from Review of East Palaearctic species of Sympycnus Loew, 1857, with a key to species. 2952 records from Colección Thomas G. Zoebisch asociada a la Colección Entomológica del Centro de Estudios en Zoología. 31663 records from MCP - Coleção de Abelhas. 31 records from Caracterización Ecológica de los Macroinvertebrados de las Fuentes Hídricas presentes en el Cerro Jánano. 26 records from Erhard Sopp. 67 records from Microplankton abundance at Station MARCH-1997-GN36199704603MNB03 in the euphotic zone of the Aegean Sea in spring 1997. Part 2 - dinoflagellates. 306 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE293. 983 records from DNA barcoding the fishes of Lizard Island (Great Barrier Reef). 134 records from Abundance of planktic foraminifera at CTD station PS55/082-1. 40 records from Abundance of living benthic foraminifera in sediment core CD86_07_BC4. 331 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_93MC. 5725 records from Pautas para el manejo y ordenamiento de una pesquería multiespecífica de crustáceos en un área natural protegida: El caso de la Ría Celestún, Yucatán. 180 records from Données naturalistes de Pascal Dupont. 209 records from Microzooplankton abundance measured on water bottle samples at station PS58/061-1. 22 records from Aglaotilla, a new genus of Australian Mutillidae (Hymenoptera) with metallic coloration. 130 records from Faunal assemblage of sediment core GS7603-13. 318 records from Bird specimens of Bihoro Museum. 239 records from (Table 2.2.2.1) Integrated abundance of sympagic meiofauna in sea-ice cores of Aurora Australis cruise SIPEX. 876 records from Phytoplankton abundance in surface water in May 1996, Ilo, Peru. 2 records from Wie viel Natur gibt es im Park?. 1764 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 1695 records from HerpMapper. 985 records from Freshwater Fishes of Bulgaria. 403 records from Nannofossil abundance of Hole 4-25. 2 records from Genetic evidence supports Sylvilagus mansuetus (Lagomorpha: Leporidae) as a subspecies of S. bachmani. 5515 records from Colección de Anfibios. 4 records from Seodaemun Museum of Natural History Fossil. 11143 records from NBMB Herps. 386 records from Foraminifera distribution of sediment core KS310. 5979 records from Efectos del Cambio Ambiental en las comunidades de organismos de los ríos mediterráneos. 7 records from Abundance of nematoda in sediment profile M3/1_018 from the Iberian deep sea basin (Table 5). 310 records from Umgebung der Gesamtschule Hamburg-Winterhude. 498 records from Bekkelag basin, Inner Oslofjord. 215 records from Naturpark Kottenforst-Ville Sammelaktion 15.-19.6.. 4 records from Description of a new species of Enispa Walker, 1866 (Lepidoptera: Erebidae, Boletobiinae) from Thailand. 29 records from Abundance of benthos infauna at station POS128/2_284. 551 records from FPN-EH-AVES - Breeding Distribution of seabirds in Patagonia Argentina coast. 648 records from Microplankton abundance in the euphotic zone of the Aegean Sea in September 1994. 62 records from Benthic foraminifera abundance of Hole 42-380. 1142431 records from VegetWeb - Repositorium von Vegetationsaufnahmen. 91 records from Zooplancton de sistemas acuáticos artificiales y naturales de Colombia. 27988 records from Bird records for Argyll for the years 2002 and 2003. 96 records from (Table 2) Palynomorph concentrations in ODP Hole 105-647A samples. 5247 records from Ibaraki Nature Museum, Fish collection. 57 records from Composition of the smaller coarse silt fraction in surface sediments of the northwest African continental margin (Appendix Tab. 4). 3 records from A new genus and new species of Potamidea (Crustacea: Decapoda: Brachyura: Potamoidae), the first stygomorphic cave crab known from China and East Asia. 13 records from Range table from planktonic foraminifers in ODP Hole 182-1128D. 128 records from Fiocruz/CCAMP - Coleção de Campylobacter. 460 records from Insectos recolectados en trampas Malaise en el departamento de Vichada - Proyecto Colombia Bio. 6 records from New records of two endemic troglobitic and threatened arachnids (Amblypygi and Opiliones) from limestone caves of Minas Gerais state, southeast Brazil. 91 records from CNIN/Tipos Homoptera. 328 records from Otter (Lutra lutra), Outer Hebrides. 743 records from Insectos recolectados en trampas Malaise en el departamento de Antioquia - Proyecto Colombia Bio. 30 records from Ornitofauna de un Área Degradada por Actividad Minera en la Costa Caucana. 87007 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 18 records from A new genus and species of large-bodied caridean shrimp from the Crozet Islands, Southern Ocean (Crustacea, Decapoda, Lipkiidae) with a checklist of Antarctic and sub-Antarctic shrimps. 6 records from Nannofossil abundance of Hole 9-79A. 3 records from Tobrilus saprophagus sp. n. and Epitobrilus interstitialis sp. n. (Nematoda, Triplonchida) from Lake Baikal, Russia. 66 records from Range table from ostracoda in ODP Hole 151-910D. 874 records from The Living Murray Fish data. 23 records from Phytoplankton abundance in surface water in 1994, Ancon, Peru. 2148 records from Lower Albian LArboudeysse (Niveau Paquier) range chart in percentages of nannofossils, in SE France. 25974 records from Long-term Bird Census in Cigu 2004-2017. 2 records from Description of the puparium of Hermetia pulchra (Diptera: Stratiomyidae) from Brazil. 124 records from Nannofossil abundance of Hole 24-233. 1464 records from CNIN/Tipos Coleoptera. 4 records from Range table from planktonic foraminifers in ODP Hole 159-960A. 1128 records from Distribution of foraminiferal fauna from ODP Hole 122-762C (Table 1). 213 records from Range table from benthic foraminifers in ODP Hole 210-1276A. 246 records from BARTH-Environnement_2017_12_18. 15 records from Four new species of the genus Trachelas L. Koch, 1872 and the first record of T. vulcani Simon, 1896 from South-West China (Araneae: Trachelidae). 82 records from A checklist of Leiodidae (Coleoptera: Staphylinoidea) of Iran. 25 records from Additional new species of the genus Obolopteryx Cohn et al. 2014 (Ensifera: Tettigoniidae) from Northeastern Mexico. 292 records from New records of sabellids and serpulids (Polychaeta: Sabellidae, Serpulidae) from the Tropical Eastern Pacific. 6199 records from SANBI: DNA Banking(1987-2011). 162 records from Total foraminifera counts of multinet M21/2_MSN658. 933 records from (Appendix A1) Calcareous nannofossil counts of ODP Site 207-1258. 38281 records from Naturalis Biodiversity Center (NL) - Mammalia. 25 records from Microzooplankton abundance and biomass at station TT043_11-1. 621 records from Nannofossil abundance of Hole 74-525A. 2082 records from Colección de Entomología - Hymenoptera - Chalcidoidea. 7 records from Taxonomy of deep-water tetillid sponges (Porifera, Demospongiae, Spirophorina) from Brazil, with description of three new species and new characters. 1 records from A new Limnonectes (Anura: Dicroglossidae) from southern Laos. 101 records from BIRDRACE Enger am Spektiv. 3803 records from Ghent university - Zoology Museum - Nematod Collection. 131 records from Total foraminifera counts from multinet M32/3_MSN956. 17 records from A stonefly species extinct in Europe (Taeniopteryx araneoides Klapalek, 1902, Taeniopterygidae, Plecoptera) is thriving in the Irtysh River in West Siberia and North Kazakhstan. 4 records from Taxonomic changes in Salyavatinae (Heteroptera: Reduviidae), with an updated generic key. 6170 records from Données naturalistes de Julien BIRARD [Inventaire Eclair 18 juin]. 7 records from Stadtrandlandschaft Apolda-Nord. 12 records from Microzooplankton abundance and biomass at station NBP97-03-13-2. 80 records from Echinoderms occurence in a strongly contaminated Bay (Portman, Spain), using ROV and Scuba-diving surveys. 5 records from A new species of Choroterpes Eaton, 1881 (Ephemeroptera: Leptophlebiidae) from India. 518 records from Nannofossil abundance of Hole 49-410. 3304 records from (Table 2) Occurrence of Late Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 322193 records from Florida Keys Reef Visual Census 2010. 38841 records from Museu de Ciències Naturals de Barcelona: MCNB-Malac. 14 records from A revision of the genus Anadenosternum Athias-Henriot (Acari: Mesostigmata: Parasitidae). 153 records from annex1. 132 records from Total foraminifera counts of multinet POS247/2_MSN1377. 2365 records from Sutton Hoo species data held by The National Trust. 39 records from Dinoflagellate abundance of Hole 28-270. 875 records from Nannofossil abundance of Hole 29-281. 8069 records from Proyecto interno ejecutado por la CONABIO: Sistema de información sobre Bosque Mesófilo de Montaña de México para apoyo en programas de restauración (Fase 1). 59680 records from Butterflies of Ireland. 315 records from (Table 3) Distribution of benthic foraminifera in ODP Hole 183-1138A. 13 records from Range table from planktonic foraminifers in ODP Hole 139-856C. 580 records from Rare plants database extract from Scottish Natural Heritage. 68396 records from CSIRO, Cruises, Vertebrate and Invertebrate Fishery Bycatch, North Australia, 1997. 27264 records from Formidabel; Belgian Ants Database. 493 records from Anfibios y reptiles de la Sierra Montenegro-Las Trincheras y el cerro el Chumil, Morelos. 216 records from A checklist of the Cleridae of Iran with new data (Coleoptera: Cleroidea). 2 records from A new species of Globicornis Latreille (Coleoptera: Dermestidae) from Baltic amber, with a key to fossil species. 1148 records from ABC event data for Nyika Plateau, Buma Hills. 126 records from Range table from planktonic foraminifers in ODP Hole 167-1021B. 4 records from A new species of Pseudocrenilabrus (Perciformes: Cichlidae) from Lake Mweru in the Upper Congo River System. 1 records from A new African Apiocera species (Apioceridae, Diptera). 164923 records from CAS Invertebrate Zoology (IZ). 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 5978 records from (Table 1) Ranges of Paleocene to middle Eocene planktonic foraminifera in ODP Hole 119-738B. 830 records from Taxonomía y distribución de los filópodos (Crustacea: Branchiopoda, Anostraca, Notostraca, Spinicaudata y Laevicaudata) de México. 118 records from Annotated catalog of the type specimens deposited at the fish collection of the “ Universidade Estadual Paulista, Câmpus de São José do Rio Preto ”, São Paulo, Brazil (DZSJRP). 1271 records from Bryophytes specimens of Okinawa Prefectural Museum & Art Museum. 31 records from Skull anatomy and phylogenetic assessment of a large specimen of Ecteniniidae (Eucynodontia: Probainognathia) from the Upper Triassic of southern Brazil. 9519 records from NSW South Coast & ACT plants. 148 records from Abundance of birds in the Lena Delta Region. 8 records from Ascidians collected during the Madibenthos expedition in Martinique: 2. Stolidobranchia, Styelidae. 81 records from Range table from planktonic foraminifers in ODP Hole 139-855C. 29 records from Succession of benthic hard-bottom communities abundance at station Errina2012_CS. 1 records from Synthèse de la Répartition des populations de chamois en 1988 (réseau Ongulés sauvages ONCFS-FNC-FDC). 184 records from Relative abundance of T. quinqueloba in sediment core PS1243-1. 42 records from An der Weida zwischen Talsperre Zeulenroda und Vorsperre Weida. 35 records from Ortsrand Zandershagen. 39 records from Planktic foraminifera counts of sediment core V19-21. 2420 records from (Figure 10) Stratigraphic ranges of selected planktonic foraminifers at ODP Hole 101-631A. 1 records from Occurrence of mammalia relicts at site Ballybetagh. 505 records from National Frog Survey of Ireland 2010/2011. 5361 records from Colección Ornitológica de la Universidad del Valle. 4 records from Parasitic copepods infesting the olfactory sacs of skates from the southwestern Atlantic with the description of a new species of Kroeyerina Wilson, 1932. 7 records from Untangling convoluted taxonomy of Chambriella Rego, Chubb & Pavanelli, 1999 (Cestoda: Proteocephalidae), with erection of Riggenbachiella n. g. and the description of a new species from pimelodid catfishes in the Neotropical Region. 207 records from Données de Mammifères marins. Mission AGOA de 2012 à 2014. 852 records from Waarneming.nl (NL) - Great Grey Shrike Count 2009-2010. 324 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of DSDP Hole 93-603C. 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-017. 2962 records from Alterra (NL) - Microarthropods inventory in calcareous grasslands. 8 records from Hemibates koningsi spec. nov: a new deep-water cichlid (Teleostei: Cichlidae) from Lake Tanganyika. 6 records from Contributions to the taxonomy of Minixi Giordani Soika and Alphamenes Van der Vecht (Hymenoptera, Vespidae, Eumeninae), with an identification key to the species of the latter. 19 records from The Goblin spider genus Xestaspis in Sri Lanka (Araneae: Oonopidae). 178 records from (Table 9) Relative abundance of benthic foraminifera in ODP Hole 112-685A. 7 records from Deep-sea ascidians from Papua New Guinea. 77 records from Revision of the Neotropical genus Macreupelmus Ashmead (Hymenoptera: Chalcidoidea: Eupelmidae). 172 records from Total foraminifera counts from multinet M31/3_MSN915. 1041361 records from NatureServe Network Species Occurrence Data. 1 records from (Table 1) Concentration of PCB and other contaminants in blood plasma of polar bears (Ursus maritimus) from Svalbard. 41676 records from Tagged Seal Location Data from SOGLOBEC. 333 records from Données naturalistes de Renaud PUISSAUVE. 310556 records from Dry Tortugas Reef Visual Census 2010. 5 records from A new species and records of Diolenius Thorell, 1870 (Araneae: Salticidae) from New Guinea. 2631 records from Universidad de Murcia, Dpto. Biología Vegetal (Botánica), Murcia: MUB-HEPATICAE. 836 records from Pollen analysis of sediment profile HAE10 from Hämelsee. 4 records from Discovery of the Dinoponera lucida male (Hymenoptera, Formicidae), a threatened giant ant from the Atlantic rain forest. 3268 records from (Table 1) Distribution of early Eocene to early middle Eocene benthic foraminifera in DSDP Hole 93-605. 1709 records from The Gibson spider collection. 50939 records from Instituto Pirenaico de Ecología-CSIC: Herbarium JACA. 68 records from Description of a new Penaeidae (Decapoda: Dendrobranchiata) species, Farfantepenaeus isabelae sp. nov.. 8 records from A new pelvic-less species of Melanorivulus Costa (Cyprinodontiformes: Cynolebiidae), with a discussion on the pelvic-fin absence in killifishes. 195 records from Truppenübungsplatz Panzerkaserne Böblingen. 1256 records from (Fig. 1) Ice rafted debris and planktic foraminifers of Hole 94-609. 651 records from Réseaux écologiques/Trame verte et bleue. 19 records from Pseudoplesiops wassi, a new species of dottyback fish (Teleostei: Pseudochromidae: Pseudoplesiopinae) from the West Pacific.. 5 records from Cnesterodon holopteros (Cyprinodontiformes: Poeciliidae: Poeciliinae), a new species from the Republic of Uruguay.. 358 records from Granulometry and foraminiferal content of sediment core PI-88-AR_P9. 7 records from Content of G. menardii in sediment core V25-70. 66164 records from Florida Keys Reef Visual Census 1996. 2867 records from Pollichia Pilzherbar. 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 783 records from Neogene palynomorpha from site 93-603, part 2. 14 records from Review of the leafhopper genus Longicornus Li & Song (Hemiptera: Cicadellidae: Deltocephalinae) with description of two new species. 3 records from Revision of the ant genus Perissomyrmex with notes on the phylogeny of the tribe Myrmecinini.. 24387 records from Données de Luc BARBARO. 34 records from Planktic foraminifera counts of sediment core ELT48.011-PC. 113 records from (Figure 3) Selected benthic foraminifera measurements from sediment core AvH248260-1, Ameralik Fjord, SW Greenland. 212 records from (Table 7) Relative abundance of benthic foraminifera in ODP Hole 112-683A. 1 records from A new species of Eigenmannia Jordan & Evermann (Teleostei: Gymnotiformes: Sternopygidae) from Río Ventuari, Venezuela. 756 records from Mokihinui and Karamaea small tributaries and seeps. 684 records from Relative abundances of late Quaternary benthic foraminifera in ODP Site 181-1119. 829 records from If_Ecologie_Conseil_2017_12_18. 5 records from On the types species of the New World dung beetle genus Canthidium Erichson, 1847 (Coleoptera: Scarabaeidae: Scarabaeinae), with an annotated checklist of species. 238 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Hemiptera (ZUFMS-HEM). 1450 records from (Table 1) Relative abundance of planktic foraminifera in Paleocene to Eocene sediments of ODP Hole 119-738C from the southern Kerguelen Plateau, Indian Ocean. 20 records from Molecular and morphological identification of pistachio armored scale insects (Hemiptera: Diaspididae), with description of a new species. 1254 records from (Table 1) Calcareous nannofossil distribution and relative abundance in ODP Hole 114-699A. 915 records from Rescate de epífitas Oleoducto Bicentenario, Tramo Araguaney - Banadía (rescate). 48 records from Total foraminifera counts of multinet M6/7_MSN140. 1510 records from Fortalecimiento de las colecciones de ECOSUR. Primera fase. 9810 records from Royal British Columbia Museum Entomology Collection. 129 records from Dinoflagellate abundance of Hole 81-552. 1 records from Lanlabeo duanensis, a new genus and species of labeonin fish (Teleostei: Cyprinidae) from southern China. 421 records from Monitoreo biológico en la cuenca La Paila, campaña ARA - RARE - CVC – Asociación Calidris. 7 records from The first elateroid beetles (Coleoptera: Polyphaga: Elateroidea) from the Upper Jurassic of Australia. 280 records from (Table 3) Meiofauna density in surface sediments of the Cretan Sea. 29 records from Occurrence of mammalia relicts at site Großes Schulerloch. 29 records from New and little known Orthoptera (Ensifera and Caelifera) from the Ñambí River Natural Reserve, Nariño, Colombia. 477 records from (Table 1) Stable isotope ratios of foraminifera in sediment core CH82-20. 2800 records from Mid-Pleistocene (800-400 ka) planktic foraminfer assemblages of IODP Site 306-U1314. 551 records from Phytoplankton abundance in surface water in January 1996, Chimbote, Peru. 5940 records from Plan Aménagement et de Gestion Simplifié (PAGS) des forêts galeries des départements de l'Ouémé-Plateau. Data mobilized in the framework of a JRS Biodiversity Foundation project in Benin. 1 records from Nothrus bicarinatus. 39 records from Nannofossil abundance of Hole 66-493A. 10 records from Review of Allanagrus Noyes & Valentine (Hymenoptera: Mymaridae) with a key to species. 3276 records from (Table 1) Distribution of Lower Cretaceous calcareous nannofossils at DSDP Hole 93-603B. 106 records from Rare vascular plant species in North-West of Kostroma region, Russia. 200 records from Assemblage of living benthic foraminifera in sediment core GeoB3706-3. 141 records from Draubiotop Lavamünd. 549 records from Netzfluegler_Raw1. 115 records from Foraminifera species abundances from tow TT011_12-MOC74. 55 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2008. 164 records from A synopsis of the subgenus Centris (Hemisiella) Moure, 1945 (Hymenoptera: Apidae: Centridini) in Colombia, with description of a new species. 8328 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Diptera_Tipulidae_Palearctic. 25 records from Fleas (Siphonaptera) of Turkey: species composition, geographical distribution and host associations. 92 records from Birdrace_TerraCamper-Münster. 6 records from Revised status of Oridryas Meyrick, 1938: new synonyms of Ypsolopha Latreille, 1796, and Ypsolopha parenthesella (Linnaeus, 1761) (Yponomeutoidea: Ypsolophidae). 301 records from Revision of Archaeoteleia Masner (Hymenoptera: Platygastroidea, Scelionidae).. 6 records from Description of lithologic section units of IODP Hole 325-M0054B. 15 records from Range table from planktonic foraminifers in ODP Hole 180-1109C. 8 records from New species, genera, families, and range extensions of freshwater bryozoans in Brazil: the tip of the iceberg?. 3131 records from AlgaTerra. 1322 records from Records from the South Australian Seed Conservation Centre. 117 records from Distribution of planktonic foraminifera of sediment core SH1972_7. 820 records from Molluscs in surface sediments off Sylt collected during HEINCKE cruise HE272. 65 records from Endophallus structure: a promising tool for cryptic species identification in Timarcha Samouelle, 1819 (Coleoptera: Chrysomelidae: Chrysomelinae). 7346 records from MfN - Fossil vertebrates III. 29 records from Description of two new species of Hetereleotris (Gobiidae) from the south Pacific, with a revised key to species and synonymization of the genus Pascua with Hetereleotris.. 60 records from The Elachistidae (Lepidoptera: Gelechioidea) of Caucasus, with description of three new species. 34 records from Borkhart. 8633 records from HSU Vertebrate Museum Mammals Collection. 8160 records from (Table 4) Distribution of benthic foraminifera in ODP Site 120-750. 226 records from Planktic foraminifera assemblage in sediment core GIK17730-4. 3464 records from Centre for Biodiversity Genomics (BIOUG) - Marine Invertebrates. 39 records from Nannofossil abundance of Hole 9-80. 6 records from Two new species of Miltochrista from India (Lepidoptera, Erebidae, Arctiinae). 128 records from (Table 2a) Downcore distribution of live benthic foraminifera of sediment core PS1394-1, Weddell Sea. 348 records from Foraminifera abundance of Hole 57-440B. 238 records from List of Macroinvertebrate Species recorded in Vava’u during BioRAP survey. 6 records from The genus Pseumenes Giordani Soika, 1935 (Hymenoptera: Vespidae: Eumeninae) in the Philippine Islands, with description of a new species. 239 records from Rutilans. 516 records from UTEP Insects (Arctos). 127 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Ulf Soltau. 25 records from Occurrence of mammalia relicts at site Bivak Cave. 15293 records from Leicestershire Bryophyte Data. 10 records from Données naturalistes de DURON Cyril. 60311 records from Herbarium specimens of Jardins botaniques and Conservatoire Botanique of Nancy (NCY). 1 records from Endemic Families of Madagascar. XIV. a New Restricted Range Species of Pentachlaena H. Perrier (Sarcolaenaceae) from Central Madagascar. 909 records from Banco de Germoplama del Jardín Botánico de Castilla-La Mancha. 98 records from New state records and updated checklist of Aphodiini and Eupariini (Coleoptera: Scarabaeidae: Aphodiinae) from Mexico. 8551 records from Insect (ENHM-IN). 346 records from Packer Collection /Madagascar. 19866 records from Insect specimens of Himeji City Science Museum. 2412 records from Ohio University Invertebrate Paleontology Collection. 3477 records from (Table 13) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-591. 4 records from Four new species of Phyllophaga Harris (Coleoptera: Scarabaeidae: Melolonthinae) from western Cuba. 75 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 26 records from Caracterización Ecológica de la Ornitofauna del Humedal Costero Obregón. 153 records from (Table 2b) Relative abundance of planktonic foraminiferas in samples of surface sediments and in sediments accumulated about 18 ky ago from typical cores in the area of the Benguela upwelling. 1 records from Subterranean millipedes (Diplopoda) of the Iberian Peninsula. 8 records from Oxynoemacheilus hazarensis, a new species from Lake Hazar in Turkey, with remarks on O. euphraticus (Teleostei: Nemacheilidae). 32 records from Occurrence of mammalia relicts at site Bettelküche. 33318 records from BrioCAT: Banco de datos de los briòfitos de Cataluña. 145 records from Abundance of broken diatom frustules measured on water bottle samples at station PS58/049-3. 60071 records from TPWD HARC Texas Coastal Fisheries Matagorda Bay Trawl. 4818 records from Fish specimens of Natural History Museum, Kishiwada City. 11 records from Redescription and neotype designation of the Antarctic springtail Folsomotoma octooculata (Collembola: Isotomidae). 5965 records from (Table 3) Planktonic foraminifers from ODP Hole 114-704A. 10710 records from Birds (MNHM-BI). 21 records from New species of the genus Gnathochorisis Förster (Hymenoptera: Ichneumonidae: Orthocentrinae) from the Neotropical Region. 1 records from Oribates coracinus. 1594 records from Abundance of algae in the Aral Sea. 28034 records from Lizard Island Research Station. 29 records from Naturerfahrung. 63 records from Plasm bearing foraminifera counts of multinet SO118_MSN1253. 11009 records from IIAPPoa. 2502 records from ISM Herpetology Collection. 203 records from Total foraminifera counts from M35/1_MSN1047. 89559 records from Steiermärkisches Landesmuseum Joanneum - Herbarium GJO. 20 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-14-13. 4050 records from Range table from benthic foraminifers in ODP Hole 159-962D. 65 records from Leben in und an der Ruwer sowie ihren Nebenbächen. 48 records from Weide am Ostufer des Zotzensees, Müritz-Nationalpark. 18120 records from UAZ Bird Collection. 19 records from Suivi des reptiles des landes du Technopôle du Madrillet. 138 records from Total foraminifera counts of multinet M12/3_MSN535. 896 records from Data on agroforestry plant species of Benin. 1266 records from Insectes Hyménoptères Formicidés de Corse. 740 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC13-229. 3460 records from Base de datos de la Sala de Colecciones Biológicas de la Universidad Católica del Norte (SCBUCN). 1 records from V ° Contributo alla conoscenza dei miriapodi cavernicoli italiani. 141 records from Total foraminifera counts from multinet M31/2_MSN888. 6 records from A new species of Olecryptotendipes Zorina from China (Diptera, Chironomidae). 17 records from Benthic macrofauna abundance of sediment core 13078-013. 1075 records from Planktic foraminifera counts of sediment core RC14-35. 197500 records from Museo Nacional de Ciencias Naturales, Madrid: MNCN_ICTIO. 5 records from Colección de Referencia de Platelmintos del Museo de Ciencias de la Universidad El Bosque. 857 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 420 records from Relative abundance of ostracods in sediment core St09. 36 records from Taxonomic notes on Palearctic Podalonia Fernald, 1927 (Hymenoptera, Sphecidae), with descriptions of four new species. 26 records from New species and record of Nazeris Fauvel in southern China (Coleoptera, Staphylinidae, Paederinae). 166 records from Microplankton abundance in the euphotic zone of the Aegean Sea in October-November 1991. 2550 records from Nematode genera abundance from Portuguese canyons HERMES HERMIONE. 43 records from Plasm bearing foraminifera counts of multinet M21/5_MSN734. 240 records from (Table 4) Distribution of calcareous nannoplankton in selected samples of ODP Hole 112-681A. 21 records from (Tab. 2) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 1-4, Blake-Bahama Basin. 315 records from Range table from planktonic foraminifers in ODP Hole 155-945A. 3066 records from Phytoplankton abundance during ARGOS cruise Argos90/8. 574 records from (Appendix 2) Diversity and foraminifera of sediment core M5/2_KL15. 3 records from New species of the spider genus Olios Walckenaer, 1837 (Araneae: Sparassidae: Sparassinae) from Laos. 258 records from Determinación de la distribución potencial de las especies nativas e introducidas de bambú en México.. 8 records from Phoronida - SMF. 383 records from Pollen counts of sediment core GeoB9503-5. 2 records from The Persian / Arabian Gulf's sole great white shark Carcharodon carcharias (Lamniformes: Lamnidae) record from Kuwait: misidentification of a sandtiger shark Carcharias taurus (Lamniformes: Odontaspididae).. 1645 records from IFO Bacteria database. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT011_10-CTD121. 332 records from 6. Tag der Artenvielfalt Hockenheim Thema: Wald 12.-14.6.2009. 67 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 794 records from Macroarthropods, Narsarsuaq 2014, Greenland. 410 records from Planktic foraminifera abundance of Hole 22-216. 1212 records from (Table 12) Distribution of planktonic foraminifera in the early Miocene section of ODP Hole 149-900A. 201 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/092-6. 36 records from Phytoplankton abundance measured in surface water during VALDIVIA cruise VA137. 281250 records from Quadrige. 2697 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Verdon_2017_12_18. 2255 records from (Appendix B) Benthic foraminifera extinction group species in combined DSDP Hole 33-317B and sediment core KR9912-PC4. 131 records from Occurrence of mammalia relicts at site Bocksteinschmiede. 40 records from Mesostigmatic mites (Acari: Mesostigmata) of Saudi Arabia (excluding Phytoseioidea), new records and a key to the known species. 1 records from Description of the larva of Orthemis ferruginea (Fabricius, 1775) (Odonata: Libellulidae). 53 records from Assemblage of total living benthic foraminifera in sediment core SO117_MC468. 66 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/574-1. 1748 records from Floral visits on plants, InsectScale 2008. 2510 records from Kenya Wildlife Service, Laikipia Samburu Aerial Census, 2012. 18 records from An interactive key to Central European species of the Pteromalus albipennis species group and other species of the genus (Hymenoptera: Chalcidoidea: Pteromalidae), with the description of a new species. 30 records from Range table from planktonic foraminifers in ODP Hole 178-1096A. 6 records from A new species of Laccobius Erichson and additional faunistic records of the genus from China, with a key to subgenus Glyptolaccobius Gentili (Coleoptera: Hydrophilidae). 3 records from Recognition of a new species of Carmenta from New Mexico supported by morphology and mitochondrial cytochrome oxidase I data (Lepidoptera: Sesiidae: Sesiinae: Synanthedonini). 1496 records from Stoneworts in Wales. 1900 records from Fungi Collection. 6 records from Two new species of tribe Agalliini (Hemiptera: Cicadellidae: Megophthalminae) with note on intraspecific variations. 85 records from Frohlinder Mühlenbach (Dortmund-Kirchlinde). 5 records from Oribatids from Switzerland II. (Acari: Oribatida). (Acarologica Genavensia XC). 19 records from Four subgenera of Bracon Fabricius (Hymenoptera, Braconidae, Braconinae) newly recorded from China, with description of five new species. 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 40281 records from LSU Shirley C. Tucker Herbarium at Louisiana State University - Lichens. 180 records from Plasm bearing foraminifera counts from multinet SO119_MSN1281. 120 records from Total foraminifera counts of multinet M10/2_MSN262. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 20 records from Description of lithologic section units of IODP Hole 325-M0033A. 2174 records from ConDidact Citizen Science Surveys - Snails 2006. 363 records from Range table from planktonic foraminifers in ODP Hole 182-1129C. 24 records from A new species of Jenynsia (Cyprinodontiformes: Anablepidae) from northwestern Argentina and its phylogenetic relationships.. 26 records from New species and records of Leuctridae (Plecoptera) from Guangxi, China, on the basis of morphological and molecular data, with emphasis on Rhopalopsole. 46 records from Total foraminifera counts of multinet M21/5_MSN742. 47 records from (Table 1.2.1.1) Abundance of sympagic meiofauna of sea-ice core PS69/549-2. 54 records from Three new species of Gastromyzon (Teleostei: Balitoridae) from southern Sarawak.. 282 records from Deponie Klausdorf. 48 records from Schulgelände (Wetter). 22 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 6 records from A new species of Polyamia DeLong (Hemiptera: Cicadellidae: Deltocephalinae: Deltocephalini) representing the first record of the genus from South America. 3093 records from Establecimiento de un área protegida en el Alto y Bajo Calima, área clave de biodiversidad en el Valle del Cauca, Colombia. 61 records from Phytoplankton abundance at station Casma_2003-04-28_2, Casma, Peru. 14387 records from Enquête Lucane. 8096 records from CSIC-Real Jardín Botánico-Colección de Algas (MA-Algae). 22817 records from Floristische Kartierung Österreichs - Mapping the Flora of Austria. 961 records from Erlengraben/Lipp-Tal (Östringen). 56582 records from Birds of Rottnest Island, Western Australia, 1981 - 2007. 1986 records from Données Cetonidae -1981-2014-LACOSTE Frédéric. 6 records from A new species of the genus Diogenes Dana, 1851 (Crustacea: Decapoda: Anomura: Diogenidae) from Gujarat, northwestern India. 147 records from Plasm bearing foraminifera counts of multinet M21/2_MSN656. 31 records from Benthic foraminifera abundance of Hole 42-379A. 392 records from Expédition Karubenthos 2012 : inventaire des Echinodermes de la Guadeloupe. 1806 records from (Table 3) Distribution of Pleistocene to late Miocene nannofossils in ODP Hole 108-657A. 24 records from New species of Neohybos Ale-Rocha & Carvalho (Diptera, Hybotidae, Hybotinae) from South America. 2548 records from BioGIS - Reptiles - HUJ collections. 19 records from Microplankton data off Mejillones, 2006, Chile. 5 records from An overview of the genus Plesionika Bate, 1888 (Decapoda, Caridea, Pandalidae) in Asian waters. 10 records from Analyses of the recent components of sediment core PS1222-1. 49 records from Coccoliths in sediment core PS1535-8. 650217 records from Flora Atlas N.T.. 1 records from Klosterlandschaft Maulbronn 19. und 20. Juni 2010. 5449 records from Fishes in the Argentine Sea from 1967 to the present time. 54 records from Redescription of Cletocamptus albuquerquensis and C. dominicanus (Harpacticoida: Canthocamptidae incertae sedis), and description of two new species from the US Virgin Islands and Bonaire. 1597 records from Dpto. de Botánica, Ecología y Fisiología Vegetal (Histórico COFC). Facultad de Ciencias. Universidad de Córdoba. 17 records from (Table 2) Madreporarian corals collected in the Canary upwelling area. 232 records from Late Cretaceous and Cainozoic bathyal Ostracoda of DSDP Site 62-463 in the Central Pacific (Fig. 3). 8 records from A new species of Dohrnemesa from Brazil, with notes on the male of D. carvalhoi and on D. albuquerquei (Hemiptera: Heteroptera: Reduviidae: Emesinae). 12 records from Two new species of Limbodessus diving beetles from New Guinea - short verbal descriptions flanked by online content (digital photography, μCT scans, drawings and DNA sequence data). 845 records from Alterra (NL) - Entomofauna inventory in arable fields Hoeksche Waard. 139 records from Occurrence of zoobenthos organisms in the sampled Central-Yakutian Lakes, Appendix 2-4. 899 records from Stable isotopes and content of foraminifera at Hole 130-805C. 550 records from Colección de Referencia de Macroinvertebrados Bentónicos del Museo de Ciencias de la Universidad El Bosque. 1191 records from Colección base (BGVPA) del Banco de germoplasma del Jardín Botánico Atlántico de Gijón. 10 records from Ostracoda abundance of Hole 32-306. 3018 records from SPC PROCFish/C Invertebrates Observations Wallis and Futuna 2005. 1584 records from Registro de vertebrados durante el fototrampeo del convenio 027 - 2014 CVC - Panthera. 170 records from Benthic foraminifera assemblages and stable isotopes of sediment core PS1290-4. 102 records from (Table 3) Abundance and biomass of Proboscia alata in patches of its mass development over the Bering Sea middle shelf, percentages of P. alata and associated algae species and their groups in total phytoplankton abundance and biomass. 3189 records from (Table AT1) Planktonic foraminiferal stratigraphy of ODP Hole 182-1126B. 1247 records from Revues diverses et littérature grise.. 70 records from Porifera Collection - Instituto Nacional de Pesquisas da Amazônia. 114 records from (Table 4) Thecosomata in ODP Hole 134-831A. 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 22 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-03-16. 1818 records from Distribution of planktic foraminifera of sediment core M33/1_SL_NAST. 8985 records from TPWD HARC Texas Coastal Fisheries Sabine Lake Gill Net. 59 records from DREAL_PACA_-_N2000_-_Pays_Provence_Verte_2017_12_18. 5 records from Tepuidessus grulai sp. nov. from Acopán Tepui in Venezuela (Coleoptera: Dytiscidae: Hydroporinae: Bidessini). 770 records from Distribution of major planktic foraminifer at Site 177-1093. 568 records from Expedición Providencia I - INVEMAR. 7 records from Description of lithologic section units of IODP Hole 325-M0050A. 1 records from Chaetanaphothrips kiyosumianus (Thysanoptera, Thripidae) new to India with first record of the male. 50 records from Lindesnes. 10 records from Planktic foraminifera abundance of Hole 15-154A. 211063 records from UMMZ Birds Collection. 404 records from (Table 2) Fossil record of foraminifera and ostracoda from Muldsberg clay pit, north Germany. 7 records from Meatopida gen. nov., a new genus to accommodate two species originally described in Atopida White, 1846 (Coleoptera: Scirtoidea: Scirtidae). 600 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Accipitridae. 1921 records from Foraminifera abundance of Hole 61-462. 640 records from Distribution of benthic foraminifera on sediment core sediment core PS2458-4. 6 records from Systematics of the Mesalina guttulata species complex (Squamata: Lacertidae) from Arabia with the description of two new species. 364 records from Coleoptera identified from the Borax Works, Norman Road site, Bexley, London. 363 records from (App 1) Relative contents of mass species of benthic foraminifera in Holocene sediments from Core ASV11-880-3. 76 records from (Table 1) Counts and concentrations of pollen, spores and dinoflagellate cysts in sediment core MD01-2378. 1006 records from Collection Graptolithina fossil SMF. 956 records from Colección de reptiles del Museo de Historia Natural de la Pontificia Universidad Javeriana. 11 records from Chinja, a new genus of spider from the Eastern Arc Mountains of Tanzania (Araneae, Zoropsidae). 82649 records from Specimen Database of Colorado Vascular Plants. 25953 records from Diatomeas (Bacillariophyceae) y dinoflageladas (Dinophyceae) frecuentes en el Pacífico mexicano (costa oeste de Baja California, Pacífico centro y sur). 171 records from Taxonomic and nomenclatorial revision within the Neotropical genera of the subtribe Odontocheilina W. Horn in a new sense— 18. Six Mexican and Central American species related to Odontocheila mexicana Laporte de Castelnau and O. ignita Chaudoir, with a description of O. potosiana sp. nov.. 20 records from Range table from planktonic foraminifers in ODP Hole 181-1119C. 9 records from Inventario Herpetológico Pauto M, La Primavera, Yopal, Casanare. 62 records from Zoo Frankfurt. 129 records from BIRDRACE Oostfreesland Bird-Lopers. 177 records from Canada_BasinMegabenthos2002. 1085628 records from Fungal Records Database of Britain and Ireland. 150 records from Total foraminifera counts of multinet M21/2_MSN643. 213 records from Tejidos de especimenes colectados en la ventana de biodiversidad Río Guamués, corregimiento El Encano, Municipio de Pasto, Nariño, Colombia. 34 records from A review of the genus Orionis Shaw (Hymenoptera: Braconidae: Euphorinae) and first records of the genus from South America and the Oriental Region. 1112 records from Occurrence Data of Small Carnivores (Mammalia, Carnivora) in the National Museums of Kenya Zoology Collection. 237 records from Capercaillie national surveys. 61999 records from La familia Asteraceae en México. Fase VI. 14850 records from JOI - Herbário Joinvillea. 4 records from Description of a new species of Liocheles Sundevall, 1833 (Hormuridae) from India. 1 records from Asya hayvanlari ve zoogeografiyasi hakkinda. Asiatische Beiträge. VIII.. 31 records from Occurrence of mammalia relicts at site Tokod-Nagyberek. 1 records from A new cryptic rock-dwelling Hemidactylus Oken, 1817 (Squamata: Gekkonidae) from northern Karnataka, India. 3 records from Microplankton counts and carbon biomass at station TT007_9-CTD108. 67 records from A review of Smicronyx Schoenherr (Coleoptera, Curculionidae) of Israel, with description of two new species. 84 records from BIRDRACE Vogelscheuchen. 10 records from Four new species of the subgenus Pachylaelaps (Longipachylaelaps) from Italy, with a new identification key to the known species (Acari: Pachylaelapidae). 6247 records from Census of medical plant species of Benin (West Africa) by SOS Biodiversity. 314 records from Planktic foraminifera abundance of Hole 21-207A. 81 records from Birdrace-Die_Ornithomaten-Herford. 5 records from First record of the millipede genus Nesorthomorpha Jeekel, 1980 in Vietnam with description of a new species (Diplopoda, Polydesmida, Paradoxosomatidae). 3760 records from (Figure 4) Ranges of Cenozoic calcareous nannofossil species observed at DSDP Hole 77-536. 103 records from Mammals (UWEP-MM). 84981 records from NINA Vanndata fisk. 510 records from Inventaires des cygnes du département de l'Eure. 6 records from New species of the genera Havelockia and Thyone (Echinodermata: Holothuroidea) and first record of T. crassidisca from the southwestern Atlantic Ocean. 62 records from Artenvielfalt in der Kinderakademie im RFZ. 33 records from A new species of Microglanis Eigenmann, 1912 (Siluriformes, Pseudopimelodidae) from rio São Francisco basin, Brazil.. 2020 records from Herbario virtual bosques secos de Colombia - Sección herbario TULV (INCIVA). 1399 records from (Table 11) Ranges of benthic foraminifers through the Oligocene in ODP Hole 115-709C. 53062 records from British Antarctic Survey Argos satellite tracking data. 1365 records from Evaluación del riesgo de extinción de setenta y tres especies de lagartijas (Sauria) incluidas en la Norma Oficial Mexicana-059-SEMARNAT-2001. 56 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Alcedinidae. 150 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México, segunda etapa 2008-2009. 16862 records from BCCM/MUCL Fungi. 260 records from Planktic foraminifera assemblage in sediment core GIK17045-3. 1 records from Zetes pallidulus. 1 records from A new jellynose, Ateleopus edentatus, from the western Pacific Ocean (Teleostei: Ateleopodiformes: Ateleopodidae). 72 records from A review of Synegiodes Swinhoe, 1892 (Lepidoptera: Geometridae), with description of two new species. 754 records from Range table from benthic foraminifers in ODP Hole 172-1054A. 3 records from Distribution of meiobenthos in sediment core M19_217-2 of the northeastern Atlantic (Table 1). 114 records from Total foraminifera counts of multinet M26/1_MSN844. 600 records from Growth and age across range extension region of Centrostephanus rodgersii in eastern Tasmania and morphometric comparison of urchins inhabiting kelp versus barrens habitats, Australia (2004-2005). 3 records from Visual Plants (144.41.33.158) - Private collection of Barbara Kueppers. 35 records from Osteology and phylogeny of Parioglossus (Teleostei, Gobioidei), with a revised key to the species.. 4 records from Microplankton abundance at bottle station SEPT-1999-K4. 14 records from Taiwanese deep-water chitons (Mollusca: Polyplacophora) and survey of chiton fauna of Taiwan. 48 records from Freiheitsring (Frechen). 5 records from Nesting biology of Paragymnomerus signaticollis tauricus (Kostylev, 1940) (Hymenoptera: Vespidae: Eumeninae). 3461 records from (Table 3) Occurrences of diatoms species in DSDP Hole 41-369A. 2 records from Erythrodiplax ana sp. nov. (Odonata: Libellulidae) from Brazilian palm swamps. 6992 records from Stone-curlew Annual Surveys. 29646 records from (Table 2) Mollusc biostratigraphy of facies underlying the 'Braunkohlensande' in the Lauenburg district, north Germany. 10 records from New species of Glossoscolex and Fimoscolex earthworms (Oligochaeta: Glossoscolecidae) from Embrapa Forestry, Paraná, Brazil. 1138 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 829 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 5 records from On the identity of Sternosternus grouvellei Guillebeau, 1894 (Coleoptera: Hydrophilidae, Phalacridae). 16 records from Taxonomic review of the genus Wasmannia.. 1363 records from (Table 2) Distribution of Eocene to Paleocene calcareous nannofossils in ODP Hole 114-699A. 197 records from Diversidad y conservación del germoplasma de henequén Agave fourcroydes Lem. y su posible ancestro silvestre Agave angustifolia Haw.. 12761 records from Données naturalistes de Franck NOEL. 343 records from Natura 2000 ZPS Jarny - Mars-la-Tour. 2 records from Tamdamaeus staryi gen. nov., sp. nov. (Acari, Oribatida, Damaeidae) from Vietnam, with remarks on certain unusual diagnostic features. 3 records from A new species of Oncopeltus Stål, 1868 (Heteroptera: Lygaeidae) in the nominate subgenus from Ecuador. 265 records from Luderbusch. 1849 records from Heigham Holmes species data held by The National Trust. 82 records from Teich im Wald zwischen Böblingen und Schönaich. 2504 records from Collections data on ecology of bottom animal of the Southern ocean. 5695 records from SPC PROCFish/C Fish Observations Vanuatu 2003. 36 records from Resurrecting the genus Enitharoides Brooks, 1953 (Heteroptera: Nepomorpha: Notonectidae): description of three new species and redescription of Enitharoides brasiliensis (Spinola, 1837), comb. nov.. 119365 records from Isle of Man wildlife records from 01/01/2000 to 13/02/2017. 13 records from (Table 4a) Abundances of Globorotalia menardii in sediment core INMD-104BX. 5934 records from Agroforestry species in Parkia biglobosa's parklands in Northern Benin. 1369 records from Chromista Collection of the Seto Marine Biological Laboratory, Kyoto University. 170 records from Planktic foraminifera abundance of Hole 94-610B. 302 records from Malawi-Cicindelidae-Biodiversity-Data. 18058 records from Fish Collection of Yokosuka City Museum. 4 records from Garra sindhi, a new species from the Jebel Samhan Nature Reserve in Oman (Teleostei: Cyprinidae). 4507 records from ARC-PPRI: National Collection of Insects: Coleoptera Collection (1879-2012). 38 records from A taxonomic review of the Korean species of the subgenus Datomicra Mulsant & Rey of the genus Atheta Thomson, with description of a new species (Coleoptera, Staphylinidae, Aleocharinae). 12 records from Meiofauna abundances at the Arctic Håkon Mosby Mud Volcano (HMMV) of sediment core PS64/323-1. 70 records from (Table 4) Coiling direction changes of Neogloboquadrina acostaensis during the latest Miocene and early Pliocene of DSDP Hole 94-608 from the North Atlantic Ocean. 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 52 records from Occurrence of mammalia relicts at site Zigeunerfels. 1 records from Description of lithologic section units of IODP Hole 325-M0052C. 140 records from SNH Invertebrate Site Condition Monitoring 2015: Blind Moss SSSI. 26918 records from Hemiptera (Heteroptera) collection of National Museum of Nature and Science. 56 records from Ictiofauna balseana y helmintos parásitos asociados. 5 records from Schulinnenhöfe (Gelsenkirchen). 160 records from Wirbach-Taubental (Bad Blankenburg). 430 records from (Table 2) Some abiotic factors and distribution of benthic foraminifers in surface layer of bottom sediments from the littoral zone of the Kunashir Island (Pacific Ocean side). 9 records from Analyses of the recent components in the sand fraction of sediment core PS1012-1. 6 records from New species of the leafhopper genera Sophonia and Stenotortor (Hemiptera: Cicadellidae: Evacanthinae) from the Oriental region. 180988 records from LSUMZ Birds Collection. 286 records from Range table from benthic foraminifers in ODP Hole 198-1210A. 15 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 31 records from Nanoplankton abundance at station GeoB2012-5. 28 records from Description of two new Calicnemia from Vietnam and central Laos with notes on their congeners in Vietnam (Odonata: Platycnemididae). 841 records from Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 10698 records from Yoann_BLANCHON_2017_12_18. 13 records from Pipunculidae (Diptera) from southern Iran, including two new species of the genus Tomosvaryella Aczél. 3 records from MSB Mammal Observations (Arctos). 305 records from Relative abundance of dead benthic foraminifera of sediment core M5/2_107MC. 61718 records from Données "faune" hors insectes pour le SINP île de France. 10 records from Données naturalistes de Sophie COHEN. 129 records from Occurrence of mammalia relicts at site Burghöhle Dietfurt. 2126593 records from RSPB Big Garden Birdwatch winter sightings in the UK in 2009. 55 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB03 in the euphotic zone of the Aegean Sea in March 1998. Part 1 - diatoms. 41 records from New and poorly known Meligethes Stephens from China, with bionomical data on some species (Coleoptera: Nitidulidae: Meligethinae). 117 records from Centre d'Estudis Avançats de Blanes. Macròfits Pirineu. 2876 records from Wikiplantbase #Sicilia. 48 records from Foraminifera and stable isotopes of sediment core PS2076-1. 2657 records from Database of Australasian Vertebrate Occurrences. 55 records from Occurrence of mammalia relicts at site Rusenschloß. 75 records from Plasm bearing foraminifera counts of multinet M21/5_MSN730. 9 records from Benthic macrofauna abundance of sediment core 12930-048. 98 records from Plasm bearing foraminifera counts of multinet POS247/2_MSN1381. 445 records from South Lanarkshire peatland records 2013. 15 records from A new genus and five new species of Anostostomatidae from the Lesser Antilles (Orthoptera: Ensifera). 1 records from Distribution of Quinqueloculina sp. in sediment core 13200-045. 1032 records from Étude entomologique des forêts publiques de Martinique, pour l'ONF. 48 records from Content of coarse fraction and G. menardii in sediment corev V25-44. 276 records from (Table 6) Ranges of benthic foraminifers through the Oligocene in DSDP Hole 22-216. 44 records from Planktic foraminifera abundance of Hole 63-472. 2980 records from Museo Nacional de Ciencias Naturales, Colección de Aves: MNCN-Ornit. 1653 records from Derbyshire Casual LEPIDOPTERA records - Casual records collated by Derby Museum.. 2 records from Two new species of the genus Daptonema Cobb, 1920 (Nematoda: Xyalidae) found in an intertidal seagrass bed on the coast of the Andaman Sea, Thailand, with reference to the taxonomic status of the genus Trichotheristus Wieser, 1956. 675 records from (Tab. 3) Occurence of microfossils in Late Jurassic sediments of DSDP Hole 11-100, Cat Gap Area, western Atlantic Ocean. 72399 records from Herbarium Specimens of Tokushima Prefectural Museum, Japan. 15647 records from Universidad Autónoma de Madrid, Madrid; Lepidópteros. 7 records from Description of a new species of Eucynorta (Opiliones, Cosmetidae) from Cortés, Honduras. 345 records from (Table 3) Relative abundance of selected benthic foraminifera in ODP Hole 104-642C. 560 records from Planktic foraminifera abundance of Hole 15-149. 3939 records from Census of plant species in Pahou forest reserve. 143 records from Computarización de la colección de myxomycetes y líquenes de Baja California. 375 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 31 records from Lepidurus arcticus survey Northeast Greenland 2013. 1 records from The taxonomic implication of frontal tubercles in Polypedilum subgenera diagnoses, with re-description of Polypedilum isigabeceum Sasa & Suzuki (Diptera, Chironomidae). 153 records from VSN-Wiese. 30 records from Additions to the list of Finnish Bibionomorpha (Diptera, Nematocera). 23 records from Taxonomic studies of Japanese Formicidae part 3: genus Vollenhovia.. 7462 records from Ibaraki Nature Museum, Fungi collection. 2 records from A new species of Liriomyza Mik (Diptera, Agromyzidae) on okra in Brazil. 814 records from Chironomid Specimen records in the Chironomid DNA Barcode Database.. 190 records from Relative abundance of ostracods in sediment core Sv09. 5148 records from Colección de Reptiles - Museo de Herpetología de la Universidad de Antioquia. 209 records from Large protozoa abundance measured on concentrated water bottle samples at station PS58/009-6. 181977 records from Amis_des_Marais_du_Vigueirat_2017_12_18. 17 records from Assemblage of living benthic foraminifera in sediment core SO119_MC501, >125 µm fraction. 32 records from A new species of long-legged terrestrial Terrapotamon Ng, 1986 (Crustacea: Brachyura: Potamidae) from limestone formations in Satun, southern Thailand. 48 records from Atelier Malacologie continentale, 14-15septembre, La Flèche (Sarthe). CEN Pays de la Loire. 7 records from Cordylancistrus nephelion (Siluriformes, Loricariidae), a new and endangered species of suckermouth armored catfish from the Tuy River, north-central Venezuela.. 323 records from Size of planktic foraminifera at CTD station PS55/083-1. 104 records from Taxonomy and molecular phylogeny of the Platystictidae of Sri Lanka (Insecta: Odonata). 318 records from Phytoplankton abundance measured on water bottle samples at station PS65/514-2. 186 records from (Table II) Abundance of epibenthic phyla and classes during RSS James Clark Ross cruise JR144. 4579 records from Estación Biológica de Doñana - CSIC, Anfibios. 28331 records from R. L. McGregor Herbarium Lichen Collection. 660 records from Peces pelágicos de la Isla Cayo Serrana durante la Expedición Seaflower 2016 - Proyecto Colombia BIO. 472 records from Abundances of shells of planktic foraminifera species in Upper Miocene sediments from the Indian Ocean and relative abundances of their groups. 413 records from Clyde Breeding Bird Tetrad Atlas 1985 - 1991 - sensitive species. 10173 records from UAM Fish Collection (Arctos). 1165 records from Coleção de Bryozoa do Museu Nacional - UFRJ. 13 records from Botia kubotai, a new species of loach (Teleostei: Cobitidae) from the Ataran River basin (Myanmar), with comments on botiine nomenclature and diagnosis of a new genus.. 70 records from Isotope tracer experiment: meiofauna counts. 557 records from Corn bunting breeding distribution in Scotland. 2324 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Reptilia (ZUFMS-REP). 69 records from Foraminifera species abundances from tow TT007_7-MOC13. 336 records from KARSTLANDSCHAFT SÜDHARZ - VOM GIPSABBAU BEDROHT (Grenzstreifen am Röseberg). 33 records from New data on the Pterophoridae fauna of Liberia (Lepidoptera: Pterophoridae). 32 records from Nannofossil abundance of Hole 94-611E. 127 records from Assemblage of living benthic foraminifera in sediment core GeoB3604-1. 9329 records from Centre de Ressources Biologiques de l'Institut Pasteur. 153 records from Selztal bei Friesenheim. 28 records from Microzooplankton abundance and biomass at station TT045_19-3. 17075 records from UCM Mammal Collection (Arctos). 20 records from Botia udomritthiruji, a new species of botiid loach from southern Myanmar (Teleostei: Botiidae).. 1161 records from (Figure 4) Distribution chart of benthic foraminifers in ODP Site 126-791. 270105 records from Natural History Museum, Vienna - Herbarium W. 4 records from Distribution of meiobenthos in sediment core M23_149 (2) of the northeastern Atlantic (Table 1). 143 records from Microfossil abundance of Hole 50-416A. 3 records from Tardigrada and Rotifera from moss microhabitats on a disappearing Ugandan glacier, with the description of a new species of water bear. 4 records from Microplankton abundance at bottle station SEPT-1999-K7. 24 records from The genus Diphasia L. Agassiz, 1862 (Cnidaria, Hydrozoa) in Northwest Africa. 8 records from Coralliidae (Anthozoa: Octocorallia) from the INDEMARES 2010 expedition to north and northwest Spain (northeast Atlantic), with delimitation of a new species using both morphological and molecular approaches. 232 records from Pollen analysis of sediment profile BLA00 from Blankensee. 7 records from Données naturalistes d'Olivier VILLEPOUX. 3 records from (Table 2) Mercury concentration in hair of Northwest Greenland polar bears (Ursus maritimus). 1825 records from Galathea II, Danish Deep Sea Expedition 1950-52. 160 records from Endofauna abundance in 2006-10 from an experiment in the Wadden Sea of List, Sylt. 274 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto29-38. 80 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM3. 104 records from Antarctic Parborlasia corrugatus. 12497 records from NCSM Non-molluscan Invertebrates Collection. 111529 records from The AAU Herbarium Database. 732 records from DSMZ Collection of Plant Viruses. 5 records from Description of lithologic section units of IODP Hole 325-M0046A. 7 records from Thylacosceles Meyrick new to China, with descriptions of four new species (Lepidoptera: Stathmopodidae). 69 records from (Table 3c) Distribution of planktonic foraminiferal tests in sediments from Core NKA-40T. 6 records from Two new species of deeper dwelling Apogon (Perciformes: Apogonidae) from Micronesia and South Pacific Ocean.. 8 records from Three new species of the family Phytoseiidae (Acari: Mesostigmata) from Turkey. 1483 records from Sistematización de la Colección Entomológica Forestal del CENID-COMEF. 451 records from Sixty new dragonfly and damselfly species from Africa (Odonata). 1376 records from Bird Monitoring 2017, Meise Botanic Garden. 4375 records from Colecção Entomológica do Museu de História Natural de Maputo. 209 records from Microzooplankton abundance measured on water bottle samples at station PS58/042-2. 724 records from Heritage Trees of Ireland. 44 records from Calcareous nannofossil assemblage in sediment core CIROS-1. 6 records from Nano and microzooplankton abundance and biomass at station NBP97-01-05-10. 3 records from Three new species of Elachistidae (Lepidoptera: Gelechioidea) from India. 429 records from Distribution of agglutinated foraminifers in sediment core Well 6406/11-1. 2215 records from Collection Polychaeta - ZSRO. 14061 records from imr_mareano_rpsledge. 21 records from Consolidated Checklist of Hard Corals of the Genus Acropora Oken, 1815 (Scleractinia: Acroporidae) in North Borneo, East Malaysia. 1 records from A new species of Eumeces Wiegmann 1834 (Sauria: Scincidae) from Iran. 17 records from Definition of the Lonchaea polyhamata species-group (Diptera, Lonchaeidae) with a description of new species. 224 records from Nannofossil abundance of Hole 55-433. 8 records from RISC Non-Native Species Records for Zebra Mussel. 844 records from (Table 2) Relative abundance of 13 species of planktonic foraminifers of sediment core GIK17938-2. 675 records from (Table 5) Planktonic foraminifer abundance of ODP Hole 162-982A. 132 records from Catalogue of the type specimens of Polycestinae (Coleoptera: Buprestidae) from research collections of the Zoological Institute, Russian Academy of Sciences. 613 records from Range table from planktonic foraminifers in ODP Hole 171-1052E. 2 records from A new species of Isthmura (Caudata: Plethodontidae) from the montane cloud forest of central Veracruz, Mexico. 61 records from Plasm bearing foraminifera counts of multinet M36/6_MSN1194. 23 records from Abundance of benthos infauna at station GIK23055-1. 50 records from Site condition monitoring of lamprey in the Endrick Water SSSI and SAC, 2012. 17 records from Three new species of Tridentella Richardson, 1905 (Isopoda: Cymothoida: Tridentellidae) from New Caledonia. 22575 records from Living plant collection of Meise Botanic Garden. 143 records from Selected Scottish freshwater fish records from 2008-2011 (collected by SEPA). 771 records from GEOECOLINK_2017_12_18. 219 records from Revision of the Mesoamerican species of Calolydella Townsend (Diptera: Tachinidae) and description of twenty-three new species reared from caterpillars in Area de Conservación Guanacaste, northwestern Costa Rica. 528 records from Revision of the Malagasy genus Trichoteleia Kieffer (Hymenoptera, Platygastroidea, Platygastridae) - Darwin Core Archives. 85255 records from The Scottish Squirrel Database. 2 records from Revision of the tree crickets of China (Orthoptera: Gryllidae: Oecanthinae). 3 records from New Earwigs in Protodiplatyidae (Insecta: Dermaptera) from the Middle Jurassic Jiulongshan Formation of Northeastern China. 96 records from BIRDRACE OAG Neuwerk. 52 records from Pittosporum sucker (Trioza vitreoradiata) records aquired by the Royal Horticultural Society. 11 records from Tanytarsini (Diptera: Chironomidae) from madicolous habitat in Southeast Brazil: new species and new records. 46 records from Planktic foraminifera counts of sediment core V26-124. 42 records from (Tab. 10) Distribution of benthic foraminifera in Lower Cretaceous sediments of DSDP Hole 32-303A, Japanese Magnetic Lineations east of Japan. 13 records from Two new, brachypterous Limnellia species from the Venezuelan Andes (Diptera: Ephydridae). 1 records from Acmaeodera (Ptychomus) kubani sp. n. from Northern Africa and the Arabian Peninsula, with notes on the taxonomic composition of the subgenus Ptychomus Marseul, 1866 (Coleoptera: Buprestidae: Polycestinae: Acmaeoderini). 36 records from Selz (Ingelheim am Rhein). 9 records from Four new species of Epacanthion Wieser, 1953 (Nematoda: Thoracostomopsidae) in intertidal sediments of the Nanji Islands from the East China Sea. 9594 records from Disko Fan Conservation Area in the Davis Strait (Eastern Arctic) - Epibenthic Megafauna Database. 398 records from Tsetse flies of East Africa update. 2647 records from SPC CoFish Fish Observations Nauru 2005. 83 records from European bison in Białowieża Primary Forest. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 2 records from Amphibia ZMK. 102 records from A Lichen Survey of the Ben Nevis Plateau. 387 records from Distribución espacio-temporal de las larvas de atunes en el Golfo de Tehuantepec, México. 3 records from Redescription of Zoica puellula (Simon, 1898) (Araneae: Lycosidae: Zoicinae) and transfer of Zoica harduarae (Biswas & Roy, 2008) to Agelenidae C. L. Koch, 1837. 8 records from On the taxonomy of the genus Acronicta (Lepidoptera, Noctuidae). IV. Acronicta digna species-complex. 20755 records from pins. 1005 records from Collection Crustacea - KAUMM. 12 records from Revision of the genus Kailasha (Lepidoptera, Erebidae, Arctiinae) from Oriental region, with description of one new species. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 2256 records from Benthos, zoo- and phytoplancton data collected during the monitoring cruise of RV "Vladimir Parshin" in 1996.. 53 records from Abundance of living benthic foraminifera in sediment core CD86_09_BC1. 546 records from tree climbing bryophytes & lichens at tree base and crown with traits. 540 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/511-12. 40 records from A review of the leafhopper genus Scaphoideus (Hemiptera: Cicadellidae: Deltocephalinae) from Guangxi of China, with description of one new species. 3264 records from SMNS Palaeontological collection - Invertebrates (Cenozoic). 310 records from Données naturalistes de Laurent PONCET. 19 records from Coccolith counts of multinet SO119_MSN1301. 2509 records from Colección de Oligoquetos Acuáticos de la UPV/EHU. 3 records from A new species of the genus Thrips (Thysanoptera: Thripidae) from the Western Ghats of India. 49 records from Mammal specimens of Natural History Museum, Kishiwada City. 1349 records from Caracterización florística y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicción Corantioquia. 1275 records from (Appendix B) Dinoflagellate cysts eco-groups of DSDP Hole 38-338. 127 records from Inventario y monitoreo de aves silvestres en tres humedales del departamento de Córdoba. 12 records from Three new species of squat lobsters of the genus Fennerogalathea Baba, 1988 (Decapoda: Galatheidae) from the Pacific Ocean. 55675 records from UWBM Mammalogy Collection (Arctos). 5314 records from Dados da ocorrência de plantas lenhosas em um gradiente de perturbação/precipitação em área de Caatinga, Parque Nacional do Catimbau, Buíque, PE, Brasil. 2 records from Acromyrmex charruanus: a new inquiline social parasite species of leaf-cutting ants. 142 records from Planktic foraminifera abundance of Hole 32-313. 11129 records from Royal Ontario Museum Fungarium (TRTC). 159 records from Données de Lépidoptères de Bruno DAUGET - Dépt du CHER (18). 486 records from El código de barras de las especies NOM-059 de mamíferos del Noroeste de México. 4686 records from Butterfly_conservation_2017_12_18. 66 records from Notes on the shrimp genus Palaemon Weber, 1795 (Crustacea, Decapoda, Palaemonidae) and related genera from Taiwan. 14052 records from Plant specimens of Horaiji-san Museum of Natural History. 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 137398 records from Cranefly (Diptera; Tipuloidea) records for Britain to 2016. 96 records from Coleoptera identified from the St. Paul's Academy site, Abbey Wood, London. 34224 records from Données bibliographiques et opportunistes Odonates issues du SiRF. 19 records from Two new species of Crocodile Skinks (Squamata: Scincidae: Tribolonotus) from the Solomon Archipelago. 138 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 3429 records from Mise en place d'un suivi scientifique des amphibiens pour la production d’indicateurs de biodiversité. 480 records from Benthic foraminifera counts of sediment core GIK23342-6. 24 records from Occurrence of mammalia relicts at site Sainte-Eulalie. 99 records from Düne am Ulvenberg (Darmstadt). 4 records from Ompok argestes, a new species of silurid catfish endemic to Sri Lanka (Teleostei: Siluridae). 1 records from A new species of Homatula from the Red River drainage in Yunnan based on morphological and genetic data (Teleostei: Nemacheilidae). 3 records from Données naturalistes d'Emilie WEBER. 43857 records from Mammals housed at MHNG, Geneva. 352 records from Phytoplankton abundance measured on water bottle samples at station PS65/424-3. 136 records from Grillhütte Wettsaasen, Wiese, Hecken. 630 records from (Table 3) Protist occurrence in bottom sea ice and surface water samples obtained during a CCGS Amundsen cruise in 2007/2008. 825 records from (Appendix A5) Relative abundances of planktonic foraminifera of sediment core GeoB1711-4. 2312 records from Mycological collection of the National Museum. 1 records from Two new species of Tenuipalpus Donnadieu, 1875 (Acari: Trombidiformes: Tenuipalpidae) from Iran. 63 records from Marine gastropod distribution from patagonian shallow waters. 9 records from A new species of Leuctra from Turkey, and notes on Anatolian Rhabdiopteryx (Plecoptera: Leuctridae & Taeniopterygidae). 6 records from Species delimitations in the Atractus collaris complex (Serpentes: Dipsadidae). 185 records from Range table from benthic foraminifers in ODP Hole 174-1073A. 55 records from Phytoplankton abundance at station Rigel_4_2005-05 in May 2005, Chipana, Chile. 9 records from Sarcodine counts and carbon biomass at station TT008_6-PMOC7. 1 records from Two new species of obligatory termitophilous rove beetles from Brazil (Coleoptera: Staphylinidae: Termitomorpha Wasmann). 410973 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Aves Reproductoras. 10006 records from DASSH Data Archive Centre volunteer survey data. 866 records from Biodiversidad vegetal de la parte alta oeste de la cuenca del Chuviscar, Chihuahua. 188 records from (Abb. 8 bot) Pollen profile Radauerborn, Harz. 121 records from Range table from planktonic foraminifers in ODP Hole 177-1088C. 121 records from BIRDRACE Immerwiederhopf. 8 records from Description Of Six New Species Of Spiders Of The Genera Lathys (Family: Dictynidae), Marpissa (Family: Salticidae), Misumenoides (Family: Thomisidae), Agroeca (Family: Clubionidae), Gnaphosa (Family: Gnaphosidae) And Flanona (Family: Lycosidae) - From India. 9 records from Plasm bearing foraminifera counts from multinet M31/2_MSN890. 16 records from Dinoflagellate cysts of surface sediments. 7 records from Collection Malakologie - SMNG. 47 records from Données d'observation de phanérogames marines en Martinique. 440 records from Antarctic and Subantarctic Asteroid zoogeography. 5 records from New species and records of Omaliini from East Asia (Coleoptera: Staphylinidae: Omaliinae). 1440 records from (Table 21) Benthic foraminifera in middle Miocene sediments of DSDP Hole 90-594. 374 records from Coastal and Marine Species Database. 229 records from Nannofossil abundance of Hole 67-499. 1300 records from Data from vegetation plots at Atiquipa, Southern Peru. 54 records from Weidegebiete in der Selzrenaturierung. 212 records from Revision of the genus Dinotoperla Tillyard, 1921 (Plecoptera: Gripopterygidae) using morphological characters and molecular data: Establishes two new genera, three new species and updates the larval taxonomy. 744 records from Ostracoda in sediment core PS51/159-10. 66 records from A global revision of the Seahorses Hippocampus Rafinesque 1810 (Actinopterygii: Syngnathiformes): Taxonomy and biogeography with recommendations for further research. 3 records from Lampetra soljani, a new brook lamprey from the southern Adriatic Sea basin (Petromyzontiformes: Petromyzontidae). 6 records from A new species of Tambitnotia from Peru, with the first reported female of the genus (Lepidoptera: Tortricidae: Olethreutinae). 834588 records from Liste des espèces de la faune sauvage (Amphibiens, Mammifères hors Chiroptères, Oiseaux, Orthoptères, Reptiles & Rhopalocères) observées selon le maillage communal français de la base de données naturalistes Faune-France .. 587 records from Ciidae (Coleoptera) records from Britain and Ireland to 2004. 78 records from Range table from benthic foraminifers in ODP Hole 174-1071C. 6 records from A new species of Mada Gordon from the Andes (Coleoptera: Coccinellidae: Epilachnini). 1 records from Description of females of Chilarboreus Ruta, 2011 (Coleoptera: Scirtidae: Scirtinae). 401 records from Revision of the family Chasmocarcinidae Serène, 1964 (Crustacea, Brachyura, Goneplacoidea). 1836 records from Phytoplankton abundance in surface water in October 1996, Ilo, Peru. 6083 records from Sepsidae (Diptera) records from Britain and Ireland to 1985. 242 records from UTEP Fish (Arctos). 14 records from Microzooplankton abundance and biomass at station NBP97-08-07-1. 50 records from Phytoplankton abundance at station Sechin_2003-08-27_2, Casma, Peru. 7 records from A review of Gonothrombium Feider, 1950 (Actinotrichida: Microtrombidiidae) with description of a new species from Turkey. 92 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 160-969A. 61417 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 1 records from A new species of Anthiadinae (Teleostei: Serranidae) from São Pedro and São Paulo Archipelago, Brazil, Equatorial Atlantic.. 2 records from Pseudolycoriella skusei sp. nov. (Diptera: Sciaridae), a new dark-winged fungus gnat from Norfolk Island and Australia. 3740 records from (Table S2a) Nannofossil species richness in the Bass River section. 7548 records from Botanic Garden of the Finnish Museum of Natural History. 89 records from Planktic foraminifera abundance of Hole 63-470A. 6250 records from Invasive species - Chinese mitten crab (Eriocheir sinensis) in Flanders, Belgium. 60 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2247-1. 157 records from Loup 2009 présence régulière communale (réseau Loup-Lynx ONCFS). 1001 records from LACM Invertebrate Paleontology. 7 records from Boraginaceae (Cynoglossum cherangauiense). 7 records from Abundance of epibenthic echinoderms at seafloor photography station POS196_1024. 43 records from Ptilophora variabilis Hartig, 1968, bona species, and description of Ptilophora nebrodensis sp. n. from Sicily (Lepidoptera, Notodontidae). 10 records from Medleria gen. nov. adds to the biodiversity of Flatidae (Hemiptera: Fulgoromorpha) in the island of Socotra. 59 records from Búsqueda de poblaciones de la liebre endémica Lepus flavigularis. 736 records from Laubenheimer Bodenheimer Ried - von Stromtalwiesen und Flutrasen. 1016 records from Inventario de las mariposas diurnas de las cañadas de Morelos y evaluación de factores que permiten el refugio de fauna con limitantes microclimáticas diferentes al macroclima dominante. 437 records from The Neotropical cuckoo wasp genus Ipsiura Linsenmaier, 1959 (Hymenoptera: Chrysididae): revision of the species occurring in Brazil. 16 records from Occurrence of mammalia relicts at site Pestera lui Climente I. 300 records from Inventory of the Heteroptera (Insecta: Hemiptera) in Komaba Campus of the University of Tokyo, a highly urbanized area in Japan. 1 records from Ubristes rex sp. n., a new microdontine hoverfly from northern Brazil (Diptera: Syrphidae: Microdontinae). 2084 records from Occurrence data of tree species for crystalline Mountain Forest of Tanzania.. 209 records from Nannofossil abundance of Hole 47-398. 9 records from The millipede family Paradoxosomatidae in the Philippines, with a description of Eustrongylosoma penevi sp.n., and notes on Anoplodesmus anthracinus Pocock, 1895, recorded in Malaysia and Sri Lanka for the first time (Diplopoda, Polydesmida). 626 records from Estado actual de conservación de liebres y conejos en categoría de riesgo en México. 1249 records from Fishes in MZNA-VERT: anatomy of cyprinids of Spain. PhD project, Rafael Miranda. 1107 records from (Table 4) Planktonic foraminifers from ODP Hole 114-704B. 14920 records from FORESTRY RESEARCH INSTITUTE OF NIGERIA- FOREST HERBARIUM IBADAN (FHI). 2 records from Arthropoden aus südostalpinen Höhlen.. 14 records from Taxonomy of Euschizomerus Chaudoir 1850 (Coleoptera: Carabidae: Panagaeinae) from India with a new species and new synonym. 660 records from MVZ Hildebrand Collection (Arctos). 80 records from Foraminifera distribution of sediment core SDSE189. 167 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Psittacidae. 6 records from Redescription, lectotype designation and new records of Anastrepha luederwaldti Lima (Diptera, Tephritidae). 23 records from Taxonomy and ecology of a new species of Corynura (Hymenoptera: Halictidae: Augochlorini) from Chile and Argentina. 10 records from First record of the spider genus Wolongia Zhu, Kim & Song, 1997 from India with the description of a new species (Araneae, Tetragnathidae). 1 records from Amycolatopsis marina sp. nov., an actinomycete isolated from an ocean sediment. 1503 records from Peces de la cuenca alta y media del río Bita, Vichada (Colombia). 27 records from Planktic foraminifera abundance of Hole 18-174. 87 records from Données 2015 de l'Observatoire de la Biodiversité des Forêts. 12217 records from California State University, Long Beach Mammals. 80 records from Total foraminifera counts from multinet SO119_MSN1303. 70 records from Revisions of Australian ground-hunting spiders. V. A new lycosoid genus from eastern Australia (Araneae: Tengellidae). 540 records from (Appendix 3) Abundances of benthic forminifera in DSDP Hole 74-525A. 5071 records from Données de mammifères enregistrées dans BazNat - Lot 2. 1357 records from Ostracoda in sediment core PS51/154-11. 84 records from Taxonomic review of the moth family Thyatiridae (Lepidoptera) from Yunnan province, China. 106 records from A review of the Cyana bianca (Walker, 1856) species-group with descriptions of a new species and a new subspecies from Indochina (Lepidoptera, Erebidae, Arctiinae). 29 records from Waldwiese. 182 records from Planktic foraminifera counts at CTD station M39/4_361CTD-18. 848 records from Nannofossil abundance of Hole 24-231. 3687 records from Clare Biological Records Centre Dataset 2004-2007. 235 records from Expédition Karubenthos 2012 : données issues des publications. 28 records from (Table 2) Distribution of the endemic fly (Anatalanta aptera) and the introduced ground beetle (Merizodus soledadinus) on the Kerguelen Islands. 16 records from A new species of the genus Rhinoleucophenga (Diptera: Drosophilidae) and redescription of five species from Neotropical region. 27476 records from Universidad de Navarra, Herbarium: PAMP-Vascular Plants. 10 records from A new species of Eidmanacris Chopard, 1956, with notes on its distribution in Brazilian caves (Phalangopsidae, Luzarinae). 174 records from Nematode abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas?. 20 records from Truchas Mexicanas. 191 records from (Table S1) Calcareous nannoplankton morphometric analyses performed of Cismon sediment core samples. 13646 records from Senckenberg - CeDAMar Resource. 5 records from On the taxonomy of Lygosoma bampfyldei Bartlett, 1895 (Squamata: Scincidae) with descriptions of new species from Borneo and Peninsular Malaysia and the resurrection of Lygosoma schneideri Werner, 1900. 516 records from Données naturalistes de Laurent KREMMER. 802 records from Biological Collection, National Institute of Oceanography, Goa, India. 1671 records from Occurrence data set for wild food plant species in Zimbabwe's biodiversity hotspots. 1016 records from ABC_Useful Plants of Malawi: Species used as Herbal aphrodisiacs. 150 records from Steinbruch Mainz-Weisenau. 1214 records from Palynological analysis of sediment core GeoB3910-2. 121 records from Total foraminifera counts of multinet M12/3_MSN557. 1518 records from (Table T5) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones P9-P11. 3862 records from Fauna y flora del municipio de Lipa, Arauca. 1 records from A new species of Crematogaster from the pinelands of the southeastern United States.. 461 records from Insect specimens of Natural History Museum, Kishiwada City. 50 records from Plasm bearing foraminifera counts from multinet SO119_MSN1285. 586 records from (Table 3h) Foraminiferal distribution chart of petroleum well Swan-3St. 38 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Corvidae. 15 records from Chenopodium. 9 records from Distribution of meiobenthos in sediment core M19_202-2 of the northeastern Atlantic (Table 1). 19 records from Occurrence of recent nannoplankton in multi-net sample at M1_NET243, Arabian Sea (Fig. 2). 188 records from Planktic foraminifera distribution of sediment core GIK17940-2. 27 records from Polychaeta abundance in surface sediments of the east Greenland continental slope (2000m section). 523 records from Anfibios de la transición Andino-Amazónica del departamento del Caquetá - Proyecto Colombia BIO. 101 records from Review of the Neotropical spider wasp subgenus Anoplius (Dicranoplius) Haupt (Hymenoptera: Pompilidae), new comb.. 3641 records from Fish: Records for Kent.. 39 records from Nannofossil abundance of Hole 39-353. 96 records from (Table 3) Abundance of living foraminifers in bottom sediments from the Kandalaksha Bay. 1 records from Planktic foraminifera abundance of Hole 54-428. 519 records from Ichthyofauna of the Kubo, Tochikura, and Ichinono river systems (Kitakami River drainage, northern Japan), with a comparison of predicted and surveyed species richness. 9 records from Family, generic and species synonymies of recently published taxa of ghost shrimps (Decapoda, Axiidea, Eucalliacidae and Ctenochelidae): cautionary tales. 14 records from Benthic macrofauna abundance of sediment core 13200-045. 6930 records from (Figure 3) Distribution of planktonic foraminifers in the Upper Cretaceous of DSDP Hole 71-511. 15 records from A survey of the family Carabodidae C. L. Koch, 1836 (Acari: Oribatida), II. 1 records from On the Chilopoda from Turkey. 2284 records from Monitoreo de la población de la guacamaya verde en la Reserva de la Biosfera Tehuacán-Cuicatlán. 1054 records from Aves de la cuenca alta y media del río Bita, (Vichada) Colombia. 271 records from (Table 3) Occurrence of benthic foraminifers in ODP Hole 116-718C. 160774 records from The Fungal Collection at the Senckenberg Museum für Naturkunde Görlitz. 2 records from Two new Isotomidae species (Collembola) from Espírito Santo State, Brazil. 33 records from Taxonomic status of maskrays of the Neotrygon kuhlii species complex (Myliobatoidei: Dasyatidae) with the description of three new species from the Indo-West Pacific. 1 records from The Cat-eyed Snakes of Madagascar: Phylogeny and Description of a New Species of Madagascarophis (Serpentes: Lamprophiidae) from the Tsingy of Ankarana. 2411 records from (App 8) Relative contents of planktonic foraminifera species in sediments from Core GeoB3011-2. 28 records from Halophila stipulacea in the Caribbean Sea. 61 records from Annotated catalogue of the click-beetle subfamily Tetralobinae (Coleoptera: Elateridae). 241 records from Taxonomic revision of the flavopalliata species group of Signiphora (Hymenoptera: Signiphoridae). 2167 records from (Table 7) Distribution of dead benthic foraminifera in deep-sea surface sediments of the Scotia Sea, part 2. 492 records from Phytoplankton abundance off Chao island in Juli 2003, Peru. 468 records from Données naturalistes de Bastien TRAN. 9 records from A new genus and new species of freshwater crab (Decapoda: Brachyura: Potamidae Ortmann, 1896) from Yunnan Province, China. 509 records from Nannofossil abundance of Hole 94-606A. 2656 records from Swiss Psyllid (Hemiptera) Collections - Basel. 10 records from Sediment properties of core PLG95B_01BOXG. 45 records from The genus Heteragrion (Odonata: Zygoptera) in Northwestern Colombia, with the description of Heteragrion tatama sp. nov.. 2 records from New species of Trichomycterus (Siluriformes: Trichomycteridae) lacking pelvic fins from Paranapanema basin, southeastern Brazil. 130 records from Plasm bearing foraminifera counts of multinet M21/1_MSN607. 1059 records from Planktic foraminifera abundance of Hole 15-148. 260 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE206. 225 records from UWIZM Mantodea. 5 records from A new and five rare bdelloids from Korea. 536 records from Distribución actual y potencial de veinte especies de hongos silvestres comestibles en los bosques de coníferas del estado de Oaxaca. 17 records from Microplankton counts and carbon biomass at station TT008_5-CTD61. 7 records from Review of the Oriental leafhopper genus Parafagocyba Kuoh & Hu (Hemiptera: Cicadellidae: Typhlocybinae: Typhlocybini), with descriptions of three new species from China. 659 records from Taxonomía y prospección del hábitat de las poblaciones de Bursera sect. Bullockia con especial énfasis en las especies afines al 'linaloe', B. aloexylon (Schiede ex Schlecht.) Engl.. 4378 records from Fauna and flora inventories (terrestrial and limnetic) from the South of Belgium. 187 records from Mollusca specimens of Kuroshio Biological Research Foundation. 1080 records from UNM Earth Sciences Collection (Arctos). 5074 records from SPC PROCFish/C Fish Observations Papua New Guinea 2006. 10293 records from Expédition Karubenthos 2012 : inventaire des Mollusques et des Crustacés de la Guadeloupe. 2398 records from (Appendix B) Stratigraphic range and relative abundance of Neogene planktonic foraminifer taxa in ODP Hole 120-748B. 55 records from New records of ant species from Yunnan, China. 250 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 3389 records from Caracterización biológica en la Serranía de San Lucas 2015. 392 records from Nannofossil abundance of Hole 22-217. 1315 records from Bird specimens of Komatsu City Museum. 40 records from Marine fish and their ectoparasitic copepods in the western Wadden Sea (North Sea) in 2010. 84 records from Total foraminifera counts of multinet M21/5_MSN728. 135 records from Boreonemoral regnskog på østsiden av Lygrespollen. 26 records from Liste des oiseaux de BZM Belambo. 2 records from Cacoplistes (Laminogryllus) brevisparamerus sp. nov., a new species of Cachoplistinae (Orthoptera: Phalangopsidae) from Guangxi, China. 72 records from Range table from planktonic foraminifers in ODP Hole 180-1108B. 83 records from Collection Crustacea - ZSRO. 1590 records from Relative abundances of twenty-eight dominant benthic foraminifera species of DSDP Hole 23-219 (Table 1s). 12 records from On the spider genus Syspira Simon, 1895 (Araneae: Miturgidae) in the Caribbean: four new species from Dominican Republic. 3965 records from SPC PROCFish/C Fish Observations French Polynesia 2003, 2004 and 2006. 10 records from Two new species of Ankareus Kerremans (Coleoptera: Buprestidae: Haplostethinae) from southern Africa. 11 records from Birds of Mount Talau National Park, Vava'u, Tonga. 1547 records from Digitalización de la Biblioteca de Sonidos Naturales del Museo de Zoología, Facultad de Ciencias, UNAM. 6 records from Cambarus (C.) appalachiensis, a new species of crayfish (Decapoda: Cambaridae) from the New River Basin of Virginia and West Virginia, USA. 11 records from Dysaphis (Dysaphis) kadyrovi sp. nov. — a new aphid species (Hemiptera: Aphididae) from Tajikistan. 152 records from Conocimiento de la diversidad y distribución actual del maíz nativo y sus parientes silvestres en México. 700 records from (Appendix B) Benthic foraminiferal abundances and principal component scores in middle to late Pliocene sediments of DSDP Hole 94-610A from the North Atlantic. 157 records from BIRDRACE Rheinische Wasserrallen. 1662 records from (Table 1) Relative abundance of planktonic foraminifers in ODP Hole 164-997A sediments. 791 records from (Appendix A) Pollen and spore counts at DSDP Hole 64-480. 12 records from A systematic appraisal of the types of ten species of Otostigmus (Parotostigmus) (Scolopendromorpha, Scolopendridae, Otostigminae). 3 records from Revision of the genus Allometopon Kertész (Diptera: Clusiidae). 1612 records from (Table 2) Distribution of planktonic foraminifers in ODP Site 112-681. 173 records from Plasm bearing foraminifera counts from M35/1_MSN1074. 2747 records from Données naturalistes de David HAPPE. 2 records from A second contender for “world’s smallest fly” (Diptera: Phoridae). 21647 records from National River Water Quality Network Database (Macro-invertebrates). 232 records from North Marine Region sawfish collection records (DEW collation), Australia (1912 - 2004). 371 records from Planktic foraminifera and paleoclimate temperature and salinity calculations from sediment core M44/1 GeoTü KL71. 66 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Especies observadas en el Parque Provincial Salto Encantado (Guller et al.a, marzo 1997). 2 records from A unique new genus and species of the phyline plant bug tribe Hallodapini from the Philippines and Thailand (Hemiptera: Heteroptera: Miridae: Phylinae: Hallodapini). 3064 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Hymenoptera (ZUFMS-HYM). 75 records from Annotated list of Mimallonidae (Lepidoptera, Mimallonoidea) from Trinidad and Tobago, with the description of a new species of Cicinnus Blanchard, 1852 and taxonomic notes. 66 records from SNH Invertebrate Site Condition Monitoring 2013/14: Whitlaw Mosses SSSI. 12 records from Fiocruz/CENT - Coleção de Enterobactérias. 30976 records from The Fungal, Lichen and Plant Collections at the Herbarium Marburgense. 264 records from DREAL_PACA_-_N2000_-_Naturalia_2017_12_18. 102 records from Waldwandel in Monschau-Mützenich-Boverei. 310 records from Manual para la identificación de lianas en el campo. 1550 records from “Phytoplankton and Zooplankton data collected during the Black Sea cruises of UkrSCES R/V "Georgyi Ushakov" in 1992”. 590406 records from Welsh Invertebrate Database (WID). 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 14 records from Lauchhamer GEO-Tag der Artenvielfalt. 1 records from Nouvelles fourmis d'Afrique.. 14 records from Bulletin mensuel de la société linnéenne de Lyon [1932- ]. 2171 records from (Table 2) Distribution of planktonic foraminifera in the upper Turonian-lower Campanian succession in ODP Hole 122-763B, Part II. 4083 records from Dipterists Forum - Recording Scheme - Stilt & Stalk Flies. 36505 records from Abundances indices and biological traits of juvenile salmon sampled in the Scorff river (France). 25 records from First Australian records of Ethusina (Crustacea: Decapoda: Ethusidae) and additional records from New Zealand. 1 records from Revisiting Gryposuchus jessei Gürich, 1912 (Crocodylia: Gavialoidea): specimen description and comments on the genus. 1171 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 3. 638 records from Benthic foraminifera abundance of Hole 56-435. 2 records from Microzooplankton abundance and biomass at station TT054_21-15. 1093 records from Systematic studies on Pseudomyrmex acacia-ants (Hymenoptera: Formicidae: Pseudomyrmecinae). 22 records from Lannapsyche and Marilia species of China (Trichoptera: Odontoceridae). 14 records from Niphargus dancaui sp. nov. (Amphipoda, Niphargidae) - a new species thriving in sulfidic groundwaters in southeastern Romania. 11260 records from Données naturalistes de Pierre FRAPA. 1305 records from (Table 2) Distribution of silicoflagellates, actiniscidians, and ebridians in selected samples from ODP Hole 112-683A. 1 records from A new miniature Melanesian Forest Frog (Ceratobatrachidae: CORNufeR) from New Britain Island, constituting the first record of the subgenus BATRAchylOdes from outside of the Solomon Archipelago. 1345 records from Collection Crustacea ZMG. 83 records from Naturpark Kottenforst-Ville 16.6.09. 12 records from Range table from planktonic foraminifers in ODP Hole 169-1038H. 1000 records from Fish specimens of Takatsuki Nature Museum (Aquapia Akutagawa). 10098 records from Araneae Collection. 1 records from A fossil caddisfly (Insecta: Trichoptera) from the Eocene of Colorado. 749 records from Planktic foraminifera abundance of Hole 15-154A. 228 records from Biodiversidad acuática del río Amacuzac, Morelos, México. 4 records from Description of Coladenia simianensis sp. nov. (Lepidoptera: Hesperiidae) from China, with an annotated checklist of the genus Coladenia Moore, 1881. 661 records from Données de l'enquête Escargots de l'ONEM (onem-france.org). 1947 records from Lapwing Recovery Project, South West Scotland, 2006-2009. 146 records from Tortugas marinas de la Isla Cayos de Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 45 records from Antarctic Euphausiacea occurrence data from ITALICA 2000 Expedition. 70 records from Neotropical spittlebugs related to Neaenini (Hemiptera, Cercopidae) and the origins of subfamily Cercopinae. 118 records from Natur aus zweiter Hand am Muldestausee. 211901 records from Limnic freshwater benthic invertebrates biogeographical mapping/inventory NTNU University Museum. 190 records from Microzooplankton abundance measured on water bottle samples at station PS58/038-3. 23 records from TBW-Schafberg. 4952 records from Mamíferos de los Parques Nacionales Lagunas de Montebello y Palenque, Chiapas. 187 records from Philinidae, Laonidae and Philinorbidae (Gastropoda: Cephalaspidea: Philinoidea) from the northeastern Pacific Ocean and the Beaufort Sea (Arctic Ocean). 90 records from Cardiocondyla atalanta Forel, 1915, a cryptic sister species of Cardiocondyla nuda (Mayr, 1866) (Hymenoptera: Formicidae).. 35 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/045-2. 13661 records from HPL - Herbário do Jardim Botânico Plantarum. 1340 records from (Figure 2) Distribution of dinoflagellate cysts in the mid-Cretaceous of ODP Hole 101-627B. 35 records from Benthic foraminifera abundance of Hole 42-381. 36 records from Total foraminifera counts of multinet M42/3_MSN1368. 753 records from Caracterización biológica de la ventana de biodiversidad Río Guamués, corregimiento El Encano, Municipio de Pasto, Nariño, Colombia. 2801 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1995-1999. Part 1. 179940 records from Marine data from Natural Resources Wales (NRW) Technical Support (Research & Monitoring) Contracts, Wales. 23 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, >125 µm fraction. 2 records from Synthèse de la répartition des populations de cerf élaphe en 2005 (réseau Ongulés sauvages ONCFS-FNC-FDC). 9424 records from Données naturalistes (Rhopalocères et Zygènes) de Sébastien LABATUT (indépendant). 3150 records from Family Primulaceae in Virtual Herbaria of CSBG SB RAS (NSK). 1 records from Description of a second species of the genus Moronius Grossi & Vaz-de-Mello, 2015 (Coleoptera: Scarabaeidae: Rutelinae: Rutelini). 775 records from A catalogue of the fishes held in the Istanbul University, Science Faculty, Hydrobiology Museum.. 3945 records from TTRS Ornithology. 313 records from Stadtpark Herzberg (Elster). 84 records from Calcareous dinoflagellate cysts of multicorer M51/3_562-5, grain fraction < 20µm. 10 records from Benthic macrofauna abundance of sediment core 13200-017. 4 records from A new species of the genus Oxyporus Fabricius (Coleoptera: Staphylinidae: Oxyporinae) in Yunnan Province, China. 528 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core RC08-145. 4051 records from Gunma Museum of Natural History, Fungi Specimen. 313 records from Aves de la expedición en lago de Tota, Boyacá - Proyecto Boyacá BIO. 13979 records from HZI (GBF) Reichenbach Collection of Myxobacteria. 37508 records from Museo Argentino de Ciencias Naturales "Bernardino Rivadavia" (MACN). Arachnology National Collection (MACNAr). 2 records from Kirchenforst. 351 records from (Table 3) Distribution of late Cretaceous nannofossils in DSDP Hole 77-538A. 425 records from Percentages of planktonic foraminifera species in sediment core V22-38. 61 records from Range table from benthic foraminifera in ODP Hole 199-1215B. 28 records from Abundance of non-diatom phytoplankton measured on water bottle samples at station PS58/061-3. 27 records from Two new genera and five new species of Tullbergiidae (Collembola) from the southern Appalachian Mountains of North America, with redescription of Tullbergia clavata Mills. 180 records from (Table 6) Abundance distribution of the 'clavate' subspecies of the genus Globigerinelloides in DSDP Hole 79-545. 9658 records from Oiseaux nicheurs de France métropolitaine 1970-1975 - nidification possible. 2610 records from (Table 2) Pleistocene nannofossil range chart for ODP Hole 134-828A. 31 records from Salud coralina de las comunidades arrecifales de la Isla Cayo Serranilla durante la Expedición Seaflower 2017 - Proyecto Colombia BIO. 690 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 35 records from Nannofossil abundance of Hole 15-146A. 3 records from Lectotypification of three species of Silene sect. Italicae (Rohrb.) Schischk. (Caryophyllaceae). 3 records from Three new species of the cutthroat eel genus Dysomma, with comments on the variation of D. taiwanense (Anguilliformes: Synaphobranchidae). 4 records from Plasm bearing foraminifera counts of multinet POS231/3_MSN1335. 3 records from Three new species of Entomobryoidea (Collembola: Entomobryomorpha) from Brazilian Caatinga-Cerrado transition, with identification keys to Brazilian Cyphoderus, Pseudosinella and Trogolaphysa species. 5 records from Revision of Chimarrogale (Lipotyphla: Soricidae) from Vietnam with comments on taxonomy and biogeography of Asiatic water shrews. 3990 records from ZUEC-HEM - Coleção de Hemiptera do Museu de Zoologia da UNICAMP. 55 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cardinalidae. 11 records from New records of deep-sea shrimps of family Solenoceridae Wood-Mason & Alcock, 1891 (Crustacea: Decapoda: Dendrobranchiata) from Southwestern Atlantic. 295 records from Coleção Zoológica de Referência da Universidade Federal de Mato Grosso do Sul - Tecidos (ZUFMS-TEC). 150169 records from UWFC Ichthyology Collection. 473 records from (Table 2) Occurrence of the most abundant nannofossil taxa in middle Cretaceous sediments of ODP Leg 129 sites. 1 records from Morphological and molecular distinction of two Fridericia species (Clitellata, Enchytraeidae) having same spermatheca type. 58 records from Mamíferos laguna El Tinije. 35 records from Monophyly, review, six new species and DNA barcode of micropterous Afromontane Afropictinus (Heteroptera: Aradidae). 5546 records from DREAL_PACA_-_N2000_-_Parc_Naturel_Régional_du_Queyras_2017_12_18. 22213 records from MPUC - Herbário do Museu da Pontifícia Universidade Católica do Rio Grande do Sul. 11119 records from Données naturalistes d'Anthony TURPAUD. 22 records from (Table 4a) Abundance of microalgae in surface layer bottom sediments at Station ST-RSh-1 in the northeast Black Sea. 752 records from (Table 5) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-841A. 614 records from Distribution of lithic fragments and the planktic foraminifera Neogloboquadrina pachyderma in quaternary sediments of DSDP Hole 94-609 (Table 2). 79 records from Vegetationsmatrix schorfheide alb hainich 2008 durchgang1. 50 records from A new genus and species of the family Symphysanodontidae, Cymatognathus aureolateralis (Actinopterygii: Perciformes) from Indonesia. 91253 records from CUMV Fish Collection. 113 records from Microplankton abundance in the euphotic zone of the Aegean Sea at Station JUNE-94-GN3619940280200320. 6922 records from MUST, Insecta. 637398 records from Données ONF Faune-Flore-Fonge. 57 records from Distribution of planktic foraminifera of sediment core GIK23400-3. 2116 records from Collection entomologique Pierre Lachiver. 50 records from Distribution of planktic foraminifera of sediment core PS1235-1 at stadium 5.5. 48 records from Deutsche Schule Budapest. 18 records from Occurrence of mammalia relicts at site Trebacki krs. 2 records from ZUEC-POP - Coleção de Polyplacophora do Museu de Zoologia da UNICAMP. 4 records from Amphicnemis valentini sp. nov. from the Cardamom ecoregion in Cambodia and Vietnam (Odonata: Coenagrionidae). 140734 records from University of Michigan Museum of Zoology, Division of Mollusks. 43 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Spheniscidae. 19651 records from Estudios bióticos (Plantas, Fauna Edáfica, Anfibios y Aves) en los Complejos de páramos Tota-Bijagual-Mamapacha. 5 records from Occurrence of mammalia relicts at site Siebenlinden 3. 122 records from M. Burton (1936). The Fishery grounds near Alexandria IX – Sponges. Notes and Memoirs No.17. Department of Zoology, British Museum. Fisheries Research Directorate. Ministry of Commerce and Industry, Egypt.. 2103 records from Flora ficológica de la huasteca potosina. 12 records from Abundance, biovolume and biomass of heterotrophic dinoflagellates at station TT007_12-CTD139. 319 records from Range table from benthic foraminifers in ODP Hole 144-874B. 293608 records from Bird tracking - GPS tracking of Western Marsh Harriers breeding near the Belgium-Netherlands border. 613 records from Données acquises via le réseau du CBNBP. 2340 records from Type Specimen Database of Museum and Institute of Zoology PAS. 62161 records from DASSH Data Archive Centre Academic Surveys. 3784 records from Herbier de Wallis et Futuna. 1 records from First record of the thread-legged assassin bug Myiophanes greeni Distant, 1903 (Heteroptera: Reduviidae: Emesinae) from India. 3 records from Distribution of Quinqueloculina sp. in sediment core 13077-019. 322 records from Occurrence of mammalia relicts at site Roc de Combe. 148 records from Freiburger GEO-Tag der Artenvielfalt am Moosweiher in Freiburg und im angrenzenden Mooswald. 9 records from New species of Tenebrionidae Latreille, 1802 (Coleoptera: Tenebrionoidea) from the Philippines. 9 records from Monotypic no longer: a new species of Panca Evans (Lepidoptera: Hesperiidae: Hesperiinae: Moncini) from South America. 513 records from Quoll sightings register for Nth QLD. 416 records from Data collected during the expeditions of the e-learning projects Expedition Zeeleeuw and Planet Ocean. 109 records from Exkursion Ebertsheimer/Grünstädter Berg. 294609 records from University of Florida Invertebrate Paleontology. 8 records from Endangered beauties: micro-CT cranial osteology, molecular genetics and external morphology reveal three new species of chameleons in the Calumma boettgeri complex (Squamata: Chamaeleonidae). 11 records from Données naturalistes de Thibault RAMAGE. 695 records from (Table 4) Distribution of planktonic foraminifera in middle Miocene sediments of DSDP Hole 94-608 in the North Atlantic. 736 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 3 records from The spider genus Hersilia in Thailand, with descriptions of two new species (Araneae, Hersiliidae). 43 records from Vogelstimmenführung durch den Tiergarten. 2 records from Anagrus turpanicus sp. n. (Hymenoptera: Mymaridae) from China, an egg parasitoid of Arboridia kakogowana (Hemiptera: Cicadellidae). 1 records from Physoschistura walongensis, a new species of loach (Teleostei: Nemacheilidae) from Arunachal Pradesh, northeastern India. 41618 records from Données naturalistes de Pierre JAY-ROBERT. 2896 records from Localizaciones satélite de un ejemplar ("Lorien") de águila azor perdicera (Aquila fasciata Vieillot, 1822) en Aragón. 96 records from Plasm bearing foraminifera counts of multinet M42/3_MSN1362. 106 records from Evaluación de la presencia de 'Marmosa robinsoni' e inventario de mamíferos en el Departamento del Atlántico. 16738 records from Inventaire des Ephémères de métropole (Opie). 9 records from Sarcodine counts and carbon biomass at station TT012_5-TM28. 185 records from (Table 2) Range chart of benthic and planktonic foraminifera of ODP Site 127-794. 4688 records from Universidad de Barcelona (Facultad de Biología): Plantas vasculares del valle de Son del Pi y áreas colindantes. 13 records from Microzooplankton abundance and biomass at station NBP97-08-34-1. 35 records from Range table from planktonic foraminifers in ODP Hole 139-857B. 51113 records from Atlas des Orthoptères et Mantides de France métropolitaine. 9 records from Six freshwater microturbellarian species (Platyhelminthes) in permanent wetlands of the Coastal Plain of southern Brazil: new records, abundance, and distribution. 315 records from (Table 1) Ostracoda community from DSDP Hole 95-612. 1418 records from Floodplain and aquatic vegetation survey, Okavango Panhandle, 2004. 31911 records from UAM Bird Collection (Arctos). 3132 records from Resolute Passage Copepod Distribution (OBIS Canada). 21 records from Twite, winter distribution in Caithness and Sutherland 2006/7. 353106 records from Dry Tortugas Reef Visual Census 2014. 16 records from A new species of chimaeroid, Hydrolagus alphus sp. nov. (Chimaeriformes: Chimaeridae) from the Galapagos Islands.. 6 records from Two new species of Loboschiza from Cambodia and Vietnam (Lepidoptera: Tortricidae: Olethreutinae: Enarmoniini). 26 records from Ostracoda abundance of Hole 48-406. 39 records from Nannofossil abundance of Hole 29-280. 131 records from Unser Schulhof - eine Apotheke. 8 records from Description of a new alpheid shrimp, Automate isabelae sp. nov. (Decapoda, Caridea, Alpheidae) found in fish stomach contents of the lane snapper Lutjanus synagris (Linnaeus, 1758), from the west coast of Florida, Gulf of Mexico. 731 records from Systematics of the family Ariidae (Ostariophysi, Siluriformes), with a redefinition of the genera.. 691 records from Black grouse national surveys. 7245 records from Sammmlung Ule Brasilien Herbarium Hamburgense HBG. 37 records from Berlin - Treptower Park / Karpfenteich. 3 records from First record of the genus Echthronomas Forster, 1869 (Hymenoptera, Ichneumonidae, Campopleginae) for the fauna of Ukraine. 15 records from Taxonomy of European Damaeidae (Acari: Oribatida) I. Kunstidamaeus Miko, 2006, with comments on Damaeus sensu lato. 8276 records from El género Bursera en México. Parte II. 103 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 323-U1341. 17 records from Dinoflagellate cysts of sediment core IOW211630-9. 464 records from PSUZC-Mammal Collection. 161 records from (Table 2) Distribution of living benthic foraminifera in surface sediment of the Elbe estuary. 6323 records from Canadian National Collection of Insects. 4 records from First description of the female of the spider Savignia zero Eskov, 1988 (Araneae: Linyphiidae). 70 records from Distribution of hydropolyp species in surface sediments of the Red Sea (Table 5). 3 records from Occurrence of mammalia relicts at site Sesselfelsgrotte. 425 records from GCP_2017_12_18. 33 records from Two new species of Epimelitta Bates from Brazil and a new synonymy in Stenopseustes Bates (Coleoptera, Cerambycidae, Cerambycinae, Rhinotragini). 361 records from (Appendix 5) Stable oxygen isotope record of Globigerina bulloides, and abundances of Neogloboquadrina pachyderma and ice-rafted debris in sediment core MD95-2039. 8881 records from Actualisation de la cartographie des Ptéridophytes de France et d'Europe occidentale. 1419 records from (Table 6) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1018A sediments. 40992 records from Museu Paraense Emílio Goeldi - Diptera Collection. 853 records from Planktic foraminifera abundance of Hole 80-549A. 294 records from Echinoderms in surface sediments off Sylt collected during HEINCKE cruise HE275. 30 records from Phytoplankton abundance in the Wadden Sea off List, Sylt, North Sea in 2000. 11 records from (Table 4a) Abundances of Globorotalia menardii in sediment core INMD-101BX. 1 records from Hoplophora straminea. 1364 records from (Figure 8c) Distribution of Cretaceous planktonic foraminifers, calpellionids and associated organisms from DSDP Hole 77-536. 146 records from Benthic foraminifera abundance of Hole 34-320. 60 records from Phytoplankton abundance at station Sechin_2003-12-28_1, Casma, Peru. 109355 records from Herbarium Senckenbergianum (FR). 167 records from Loup 2008 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 276 records from DREAL Auvergne - Reptiles - 2015. 140626 records from Invertebrate Zoology Division, Yale Peabody Museum. 19947 records from Merseyside BioBank Active Naturalists (unverified). 6738 records from Regeneración de especies arbóreas del bosque mesófilo en las montañas del norte de Chiapas. 1 records from Zetes cespitum. 71 records from Benthic hydroids (Cnidaria, Hydrozoa) from the Ross Sea (Antarctica) collected by the New Zealand Antarctic expedition BioRoss 2004 with RV Tangaroa. 350 records from (Table 1) Distribution of Cretaceous redeposited benthic foraminifers at DSDP Hole 89-585. 523 records from Relative abundance of planktic foraminifera in the 120 kyr time slice reconstruction of sediment core V23-82. 40914 records from Managing West African Bees in the implementation of a first reference collection: Bees caught in three areas of Burkina Faso. 327 records from Ectomycorrhiza species on all VIP´s April 2008. 134 records from SDSM Botany and Paleobotany Collections. 350 records from Pollen profile 1 from Richland Creek. 177 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Emberizidae. 576 records from Ecological inventory of Borassus aethiopum (Mart.) populations in the Pendjari Biosphere Reserve, Benin. Data mobilized in the framework of JRS Benin project. 12995 records from Mammalia Collection of Institute of Systematics and Evolution of Animals. 1054 records from Mound building termites contribute to savanna vegetation heterogeneity- woody plants, forbs and graminoids. 216 records from (Table A2) Stratigraphic distribution of major planktic foraminifer species of ODP Hole 198-1210A. 1703418 records from FloraCAT: Banco de datos de los cormófitos de Cataluña. 38 records from Lesser Spotted Woodpecker sample survey in England 2007. 29 records from A review of the arboreal Afrotropical ant genus Axinidris.. 30 records from Microzooplankton abundance and biomass at station TT043_21-22. 5235 records from Phytoplankton abundance during Professor Vodyanitskiy cruise PV13. 29 records from Smear slide analysis on sediment core GeoB4223-2. 882 records from (Table T16) Planktonic foraminifera stratigraphy of ODP Hole 198-1211A, Zones P9-P12. 5578 records from Parc_Naturel_Régional_du_Queyras_2017_12_18. 11023 records from North Marine Region sea snake collection records (DEW collation), Australia (1877-2007). 72307 records from Reef Life Survey - Survey Records. 99300 records from Landesmuseum Kärnten. 15 records from Assemblage of living benthic foraminifera in sediment core CD146_55907#1, 63-150 µm. 1428 records from (Table 1) Distribution of benthic foraminifers in ODP Hole 107-650A. 1846 records from Biodiversidad en las propuestas para declaratoria de Áreas Protegidas en los Municipios de Dagua, Restrepo, La Cumbre y Vijes y un Grupo de Reservas Naturales de la Sociedad Civil. 1 records from Arthropoden aus südotsalpinen Höhlen gesammelt von Karl Strasser. 4. Aufsatz. 3 records from Taxonomy of the Sand Sliders of Western Australia’s central coast (genus Lerista, Squamata: Scincidae): recognition of Lerista miopus (Günther, 1867). 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 198 records from Planktic foraminifera distribution of sediment core 75KS5. 32 records from Nannofossil abundance of Hole 26-250. 4 records from New species and records of the Pericoma trifasciata group from Croatia (Diptera: Psychodidae). 2 records from Studies on the ant fauna of Melanesia V. The tribe Odontomachini.. 16 records from Nano and microzooplankton abundance and biomass at station NBP96-04A-17-4. 2382 records from Bay of Fundy Species List. 420 records from Pollen analysis of sediment profile BLA0 from Blankensee. 3 records from Revision of the genus Celebargiolestes Kennedy, 1925 (Odonata: Argiolestidae). 11 records from Notes on the Rhyacophila angulata Species Group with descriptions of two new species (Insecta, Trichoptera, Rhyacophilidae). 3 records from Ostracoda abundance of Hole 13-134. 420 records from Reptilia Collection of Museum and Institute of Zoology PAS. 313 records from VIP topsoil data jointsampling soilfauna, 2008. 9 records from Study of Laemostenus species across Zagros and Central zone of Iran, with the description of seven new cavernicolous species and notes on subgenus Iranosphodrus (Coleoptera: Carabidae: Sphodrini). 88 records from Revision of the genera Pareuthria Strebel, 1905, Glypteuthria Strebel, 1905 and Meteuthria Thiele, 1912 (Gastropoda: Buccinulidae) with the description of three new genera and two new species from Southwestern Atlantic waters. 81 records from Planktic foraminifera abundance of Hole 14-136. 10 records from Integrative taxonomy reveals two sympatric species of the genus Eucriotettix Hebard, 1930 (Orthoptera: Tetrigidae). 622 records from Composition of the coccolith flora in sediment core K708-007. 90529 records from UPCB - Herbário do Departamento de Botânica. 385 records from Crustacea in surface sediments off Sylt collected during HEINCKE cruise HE278. 11 records from A new species of Probolomyrmex from Madagascar.. 5 records from Notes on the genus Yunnantettix Zheng (Tetrigidae: Cladonotinae), with descriptions of two new species from Thailand. 1490 records from Database of Eurasian beaver (Castor fiber L., 1758) in Natural Reserves and National Parks of Russia. 291 records from Phytoplankton abundance at bottle station A1/52. 1023 records from Poliquetos invasores (Annelida: Polychaeta) del Puerto de Mazatlán, Sinaloa. 7357 records from ZFMK Coleoptera collection. 322 records from Nannofossil abundance of Hole 67-497. 261 records from Range table from planktonic foraminifers in ODP Hole 170-1043A. 144 records from Lustbach-Umland. 125 records from annex3. 36169 records from Herbarium of Vascular Plants Collection of the University of Extremadura (Spain). 43162 records from Ireland's BioBlitz. 23 records from Benthic macrofauna abundance of sediment core 13200-075. 2258 records from Muscidae (Diptera) records from Britain and Ireland to 1985. 336 records from Eschlberg Thalhausen. 94 records from Review of selected species of Campsurus Eaton 1868 (Ephemeroptera: Polymitarcyidae), with description of eleven new species and a key to male imagos of the genus. 234 records from Loup 2012 présence occasionnelle communale (réseau Loup-Lynx ONCFS). 18 records from Integration of molecular, bioacoustical and morphological data reveals two new cryptic species of Pelodytes (Anura, Pelodytidae) from the Iberian Peninsula. 4 records from A new genus and species of Acaenitini (Hymenoptera, Ichneumonidae, Acaenitinae) from China. 34 records from Microplankton abundance at Station MARCH-1998-GN36199804610MSB01 in the euphotic zone of the Aegean Sea in March 1998. Part 3 - coccolithophores and other groups. 188 records from Absolute abundance of dead benthic foraminifera of sediment core M5/2_91MC. 506 records from (Table T1) Planktonic and benthic foraminifer abundance of ODP Hole 183-1138A. 151 records from Revision of the genus Odocnemis Allard, 1876 (Coleoptera: Tenebrionidae: Helopini) from Turkey, the Caucasus and Iran with observations on feeding habits. 2303 records from Benthic foraminifers of sediment core Svanic90_9004. 70 records from Range table from planktonic foraminifers in ODP Hole 173-1067A. 7 records from Microcambeva ribeirae sp. n. (Teleostei: Siluriformes: Trichomycteridae): a new sarcoglanidine catfish from the Rio Ribeira do Iguape basin, southeastern Brazil.. 3 records from A new species of Angaeus from Malaysia with possible affinity to related genera within Stephanopinae (Araneae: Thomisidae). 74 records from Abundance of Lanice in 2007-03 from an experiment in the Wadden Sea off List, Sylt. 139 records from Review of the genus Eburodacrys White, 1853 (Coleoptera: Cerambycidae: Cerambycinae). 424 records from (Table 8) Sample mass, sand fraction and relative abundances of planktonic foraminifera in ODP Holes 127-794A and 127-197B. 1655345 records from Garden Bird Surveys. 862 records from (Table 3) Calcareous nannofossil distribution on ODP Hole 117-720A. 801 records from Planktic foraminifera counts during POLARSTERN cruise ARK-XIII/2. 19 records from Occurrence of mammalia relicts at site Nazeing. 1402 records from Database on reference specimens for medicinal plants of the Rubiaceae family, conserved at the CNARP herbarium. 9 records from Vigna yadavii (Leguminosae: Papilionoideae), a new species from Western Ghats, India. 41 records from A new genus and species within the tribe Earomyiini (Diptera, Lonchaeidae). 525 records from Flora y fauna asociada al hábitat del Manatí antillano en la Ciénaga de Paredes, Magdalena Medio Santandereano. 106 records from Microplankton abundance at Station MARCH-1997-GN36199704601MSB06 in the euphotic zone of the Aegean Sea in spring 1997. Part 2 - dinoflagellates. 220 records from Inventario de Mamíferos Mámbita. 2 records from A new morphologically cryptic species of Phyllomedusa (Anura: Phyllomedusidae) from Amazonian forests of northern Peru revealed by DNA sequences. 59469 records from Canadian Museum of Nature Mammal Collection. 205 records from Pollen and spore abundance of Hole 42-381. 189 records from Naturpark Sternberger Seenland. 398 records from (Appendix A) Calcium carbonate concentrations and accumulation rates of ODP Site 115-711. 1599 records from Inventaire des bois par espèce végétale de la forêt classée de Ziama en Guinée Forestière (BID-AF2015-0066-REG). 270171 records from Biodiversitätsdatenbank des Landes Salzburg. 21 records from Nannofossil abundance of Hole 52-418. 12 records from Les occurrences des Gymnospermes de l'herbier du Centre National de Floristique (Côte d'Ivoire). 97 records from Microzooplankton abundance measured on water bottle samples at station PS65/546-2. 28 records from Taxonomy of Paraplatyarthrus Javidkar and King (Isopoda: Oniscidea: Paraplatyarthridae) with description of five new species from Western Australia, and comments on Australian Trichorhina Budde-Lunde, 1908 (Platyarthridae). 4417 records from Aves del Parque Nacional Cumbres de Monterrey, Nuevo León, México. 458 records from DMNS Parasite Collection (Arctos). 204 records from Microplankton abundance in the euphotic zone of the Aegean Sea in winter 1995. 4 records from A new brachypterous species of Phoberus MacLeay (Coleoptera: Trogidae) and status changes of species in the East African P. nigrociliatus group. 18 records from Predatory Dinosaurs of the World. 20 records from Biology and population studies of two endemic orchid species on sub-Antarctic Macquarie Island. 3 records from Dinoflagellate abundance of Hole 14-136. 3294 records from Estudio taxonómico y zoogeográfico de áreas selectas de peces marinos en Laguna Madre y Costas de Tamaulipas, Veracruz y Campeche, México. 941 records from Nannofossil abundance of Hole 64-476. 1660 records from Revisión de la subfamilia Asopinae (Hemiptera-Heteroptera-Pentatomidae) para México. 16685 records from Colección general del plantas vasculares del Herbario JBB. 2960 records from Appendix A: Results of the pollen analysis of the PG1755 core from Lake Billyakh. 2188 records from Données naturalistes de Matthias COLIN. 53 records from Draposa, a new wolf spider genus from South and Southeast Asia (Araneae: Lycosidae). 1863 records from Cowan Tetrapod Collection - Herpetology. 170 records from Total foraminifera counts from multinet M31/3_MSN898. 241 records from (Table 1) Distribution of benthic foraminifera in Eocene-Oligocene sediments of DSDP Hole 12-119 in the Bay of Biscay. 761311 records from CSIC-Real Jardín Botánico-Colección de Plantas Vasculares (MA). 72 records from Plasm bearing foraminifera counts of multinet M36/2_MSN1107. 12454 records from SPC NECTALIS Zooplankton/Micronekton specimens, New Caledonia 2014. 678 records from Upper Silesian Museum, Bird Collection. 197 records from Phytoplankton abundance at station CD46_0705C#4. 1 records from Eudorylaimus kahaqensis sp. n. (Nematoda: Dorylaimida: Qudsianematidae), an interesting new species from Iran. 3 records from New synonymies in the plant bug family Miridae (Hemiptera: Heteroptera) from Northern China. 258 records from Abundance of empty diatom frustules measured on water bottle samples at station PS58/049-3. 2 records from Ein Beitrag zur Landtierwelt von Korfu. Chilopoda. 13 records from Données additionnelles d'Echasse blanche Himantopus himantopus 1980-1991 nicheuse probable ou certaine (hors période atlas 1985-1989). 2 records from A review of the genus Syrianarpia Leraut (Crambidae: Scopariinae) with description of S. elburzalis sp. n. from Iran. 1139 records from Shellfish (MNHM-MS). 29 records from Hemmerder Schelk (Unna). 50 records from The harvestman genus Taracus Simon 1879, and the new genus Oskoron (Opiliones: Ischyropsalidoidea: Taracidae). 5 records from New taxa and notes on crickets of the subfamily Landrevinae (Orthoptera: Gryllidae) from Brunei Darussalam, Borneo. 10 records from Annotated checklist of the false blister beetles (Coleoptera: Tenebrionoidea: Oedemeridae) from Iran. 3 records from First record of Gauguin's blunt-nose lizardfish, Trachinocephalus gauguini Polanco, Acero & Betancur 2016 (Teleostei: Synodontidae) outside the Marquesas Archipelago. 6120 records from Muséum de Nîmes. 2304 records from Ridge to Reef Marine Monitoring of Fanga'uta Lagoon, Tonga, October 2017. 4537 records from Institut Botanic de Barcelona (IBB-CSIC-ICUB), BC-Lichen. 2490 records from Diagnóstico del aprovechamiento de flora y fauna por los mayas del Ejido Petcacab y evaluación de la cacería y pesca, Felipe Carrillo Puerto, Quintana Roo. 51 records from Plasm bearing foraminifera counts of multinet M21/5_MSN732. 16 records from Two new deep-water species of the genus Thorogobius (Teleostei: Gobiidae) from the upper continental slope of the Eastern Central Atlantic. 2 records from Bolletino del Museo Civico di Storia Naturale di Verona, Botanica Zoologica [2000-]. 65 records from Integrative taxonomy reveals cryptic diversity in neotropical grasshoppers: taxonomy, phylogenetics, and evolution of the genus Sphenarium Charpentier, 1842 (Orthoptera: Pyrgomorphidae). 277 records from Programme de valorisation des zones humides chassées - volet Oiseaux. 12 records from A new South American species of Palaeophileurus Kolbe (Coleoptera: Scarabaeidae: Dynastinae: Phileurini). 2 records from First record of Cephenniini on Christmas Island, with updated checklist of world Cephennomicrus species and summary of their distribution (Coleoptera, Staphylinidae, Scydmaeninae). 478 records from Chinese species of Pediobius Walker (Hymenoptera: Eulophidae). 150 records from Schulgarten Huttenheim (Philippsburg/Baden). 2 records from A revision of the genus Boroecia Poulsen 1973 (Ostracoda, Halocypridae) with the descriptions of three new species. 881 records from Moluscos Marinhos de Augusto Nobre. 13459 records from Plant (JNHM-PL). 513 records from Poissons et Crustacés d'eau douce de la Martinique. 468 records from Macrobenthos in surface sediments off Sylt collected during HEINCKE cruise HE255. 8 records from American Asteraceae-feeding Astrotischeria species with a highly modified, three-lobed valva in the male genitalia (Lepidoptera, Tischeriidae). 1988 records from (Table 1) Planktonic foraminifera community at DSDP Hole 94-608. 107 records from Total foraminifera counts from multinet M31/2_MSN890. 5 records from Two new orthoclad species from Colombian Andes (Diptera: Chironomidae). 1057 records from Inventario y evaluación de fauna silvestre en el campo de exploración petrolera Niscota Sur. 2713 records from Relative abundances of planktonic foraminifera in ODP Site 121-758 (Table 1). 16276 records from Coleoptera collection of Uunio Saalas. 1 records from Ueber Chilopoden aus westbalkanischen Hoehlen. 45 records from Estimated plankton abundance at station PS63/064-6. 1070 records from CNAN/Araneae. 28 records from Anfibios y reptiles de la expedición en el páramo de Bijagual, Boyacá - Proyecto Boyacá BIO. 18139 records from The Spider Collection at the Staatliches Museum für Naturkunde Karlsruhe. 585 records from Checklist and taxonomic changes for Central and South American Philonthina (Coleoptera: Staphylinidae). 8 records from Validation of the names of eight species of Blattaria according to the Rules of Zoological Nomenclature. 6 records from Anurogryllus Saussure, 1877 (Orthoptera: Gryllidae: Gryllinae) from southern Brazil: new species and new records. 79 records from Foraminifera abundance of sediment core C1960.201. 505 records from Microplankton abundance in the euphotic zone of the Aegean, Levantine and Ionian Seas in March-April 1987. 1 records from Channa pseudomarulius, a valid species of snakehead from the Western Ghats region of peninsular India (Teleostei: Channidae), with comments on Ophicephalus grandinosus, O. theophrasti and O. leucopunctatus. 655 records from Abundance of organic-walled dinoflagellate cysts of sediment core PS2082-1. 1749 records from Benthic foraminifera abundance of Hole 84-570. 1091 records from (Table 2) Benthic foraminiferal species observed in the Quaternary samples from DSDP Hole 95-613. 1359 records from GEO Biodiversity Day. 1 records from The millipede Typhloglomeris caucasica Golovatch, 1975 found epigeically (Diplopoda, Glomerida, Glomeridellidae). 28 records from New records of lampriform fishes (Teleostei: Lampriformes) from the Pacific coast of lower Central America, with comments on the diversity, taxonomy and distribution of the Lampriformes in the eastern Pacific Ocean. 24 records from Range table from planktonic foraminifers in ODP Hole 171-1052C. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 459 records from IASTracker. Invasive Alien Species database. 13204 records from Algunas especies de anfibios y reptiles contenidos en el Proyecto de Norma Oficial Mexicana PROY-NOM-059-ECOL-2000. 159 records from Planktic foraminifera assemblage in sediment core SU90-I06. 89762 records from Ornitho.eus. 7170 records from The Bergius Herbarium. 105 records from Conocimiento integral del tapir (Tapirus bairdii) y el pecari de labios blancos (Tayassu pecari) en México. 188114 records from Terrestrial and liminic invertebrates systematic collection NTNU University Museum. 89 records from Total foraminifera counts of multinet POS247/2_MSN1384. 3 records from Distribution of Quinqueloculina sp. in sediment core 13200-073. 362 records from Museo Argentino de Ciencias Naturales (MACN), Buenos Aires: sea stars collection (Asteroidea, Echinodermata). 6 records from Three new species of Claudiella Reichardt & Vanin, 1976 (Coleoptera, Torridincolidae) from Brazil. 196 records from Planktic foraminifera counts of sediment core V16-20. 256 records from (App 6) Relative contents of benthic foraminifera species in sediments from Core PS2718-6. 101 records from Revision of the genus Acylophorus Nordmann, 1837 from Madagascar and Mascarene Islands (Coleoptera: Staphylinidae: Staphylininae: Acylophorina). 21 records from The Resin and Carder bees of south India (Hymenoptera: Megachilidae: Anthidiini). 1 records from Laimosemion leticia (Teleostei: Cyprinodontiformes: Rivulidae), a new species from the upper Rio Amazonas, Southern Colombia. 75 records from Naturpark Kottenforst-Ville 19.6.09. 228 records from MNA (Section of Genoa) and NIWA Invertebrate Collection - Ross Sea Tanaidacea. 173 records from Review of the mirine plant bug genus Eurystylus Stål from Japan and Taiwan (Hemiptera: Heteroptera: Miridae: Mirinae), with descriptions of two new species, a new synonymy and a new combination. 3 records from Contribution to the knowledge of the genus Visiana Swinhoe (Lepidoptera: Geometridae: Larentiinae), with the description of two new species from Indonesia. 73 records from Survey of slender naiad, Najas flexilis, in Loch of Butterstone and Loch of Craiglush. 62 records from Genotipificación de especies de la ictiofauna del Sistema Pánuco-Tamesí a través de la generación del código de barras de ADN mitocondrial. 18900 records from UCBG TAPIR Provider. 167 records from Morfología funcional de mantos de rodolitos en el golfo de California, México. 6255 records from Banco de datos de la ictiofauna del Río Bravo desde 1902 a 1992 en la colección ictiológica de la UANL. 333 records from renaturierter Main (Kemmern bei Bamberg). 353 records from Contribución a la distribución, ecología y estado de conservación de dos especies del género Sceloporus, endémicas de la región del Cabo, Baja California Sur. 155 records from (Appendix 1) Coral analysis and isostatic rebound effects from different Holes of IODP Expedition 310. 447 records from Mammals in MZNA-VERT: biology of Arvicola sapidus in Navarra. PhD project, Juan Manuel Garde. 665 records from Geochemistry and sedimentology on core POS200/10_28-1. 533 records from (App 3) Relative contents of benthic foraminifera in sediments from Core ASV1200. 244573 records from Oskarshamn herbarium (OHN). 1 records from Synthèse de la Répartition des populations de chamois en 2006 (réseau Ongulés sauvages ONCFS-FNC-FDC). 277 records from Rwanda's wetlands biodiversity data from different inventories that were conducted between year 2008 and 2017. 158 records from Michael Barkla's Observations. 461 records from Distribución de peces dulceacuícolas introducidos en las cuencas del México central, con especial atención a las localidades dentro del área de distribución de los peces endémicos de la familia Goodeidae. 9446 records from Batsites inventory for England (1949-2011). 5580 records from (Table 7) Occurrence of selected diatom species in ODP Hole 119-744A. 6 records from A new species of salamander of the genus Hynobius (Amphibia, Caudata, Hynobiidae) from South Korea. 103 records from Birdrace-Borussia_Zippammer-Bad Kreuznach. 328 records from Abundance of calcareous dinoflagellates of sediment core GeoB1214-1. 8 records from Records of Wenchengia (Lamiaceae) from Vietnam. 59016 records from Isopoda (Interim dataset). 1219 records from Ortopteroides de Oaxaca, México: Orthoptera, Mantodea y Phasmatodea. 129 records from Plant macrofossil concentrations from an open section of Lac de Fully sediments. 250796 records from Données du CEN Picardie concernant la Faune, Flore, Fonge. 253 records from Planktic foraminifera counts of sediment core RC14-7. 1 records from A New Genus and Species of Clingfish (Teleostei: Gobiesocidae) from Western Australia. 3142 records from Algae collection. 5080 records from Riqueza específica, distribución y abundancia de aves terrestres y marinas en Isla San José, Golfo de California, Baja California Sur, México. 311 records from Names of hydroids (Cnidaria, Hydrozoa) established by Charles McLean Fraser (1872 - 1946), excluding those from Allan Hancock Expeditions. 2 records from A new species of Phyllodytes Wagler, 1830 (Anura, Hylidae) from the Atlantic Forest of southern Bahia, Brazil. 6 records from Taxonomic contribution to the genus Sphaerosyllis (Annelida: Syllidae: Exogoninae) in the Black Sea. 9269 records from Relative abundance of benthic foraminifera in sediment core M5/2_KL15. 15 records from A key to the East Palaearctic and Oriental species of the genus Rhysipolis Foerster, and the first host records of Rhysipolis longicaudatus Belokobylskij (Hymenoptera: Braconidae: Rhysipolinae). 10 records from Nannofossil abundance of Hole 6-49. 4470 records from Données naturalistes de Jean-Paul LECHAPT. 55 records from Range table from planktonic foraminifers in ODP Hole 182-1130C. 5 records from Immature stages of the Australian flower-loving fly Apiocera striativentris (Diptera: Apioceridae). 3 records from Distribution of Quinqueloculina sp. in sediment core 12930-065. 68 records from Planktic foraminifera abundance of Hole 16-161. 31 records from The identity of catfishes identified as Mystus cavasius (Hamilton, 1822) (Teleostei: Bagridae), with a description of a new species from Myanmar.. 24642 records from FNJV - Fonoteca Neotropical Jacques Vielliard. 323 records from Eco-Stratégie_2017_12_18. 84 records from Synopsis of the bee genus Thygater Holmberg 1884 (Hymenoptera, Apidae) in the Brazilian state of Minas Gerais, with the description of a new species and a key to all Brazilian species. 78 records from (Table 3) Downcore distribution of live benthic foraminifera of sediment core SW_2b, California continental borderland. 24 records from Dinoflagellate cysts of sediment core IOW211670-7. 908 records from Códigos de barras del ADN de mamíferos topotipos de México Fase I: Noroeste mexicano. 5 records from Planktic foraminifera abundance of Hole 19-184B. 10786 records from Camera trapping bird data. 85 records from Planktic foraminifera counts of sediment core V27-47. 517 records from Crustáceos macrobénticos de la plataforma y talud continental del Golfo de México. 1 records from Validation of Tethya samaaii Ribeiro & Muricy, 2011, replacement name for the sponge Tethya rubra Samaai & Gibbons, 2005 (Demospongiae, Tethyida, Tethyidae). 8 records from (Table 1) Mean age, body measurements, and body condition index of polar bear (Ursus maritimus) mothers and cubs. 2920 records from (Table 3) Distribution of calcareous nannofossils at ODP Hole 125-782A. 385 records from (Table 4b) Distribution of benthic foraminifera of sediment core PS2212-3. 120 records from Succession of benthic hard-bottom communities abundance at Liliguapi, Paso Comau, Chile, in 2012. 23 records from AlgaTerraMovies. 1 records from On the Chilopoda from Turkey. 266 records from (Table 3) Planktonic foraminifer abundance of ODP Hole 162-980A. 455 records from (Table 2f) Nannofossil distribution chart of petroleum well Montara-2. 42 records from A review of the Barsine obsoleta species-group with description of a new species from Vietnam (Lepidoptera, Erebidae, Arctiinae). 7 records from (Table 1) Biometrics and lipid content of polar bear (Ursus maritimus) adipose tissue between 1991-2007. 239 records from (Table 8) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-851B. 1 records from A new garden eel, Heteroconger fugax (Congridae: Heterocongrinae), from the northwestern Pacific Ocean. 16998 records from Modern foraminifera in the New Zealand EEZ. 330 records from Range table from benthic foraminifers in ODP Hole 182-1126B. 15 records from Benthic macrofauna abundance of sediment core 13200-047. 16 records from Contributions to the millipede genus Nepalella Shear, 1979 from China, with four new species and first results on phylogeny based on DNA-barcoding (Diplopoda, Chordeumatida, Megalotylidae). 27 records from synthese_Protistdiversity_KG. 6279 records from SPC CoFish Fish Observations Palau 2007. 21 records from Revision of the Palaearctic and Oriental species of the genus Oides Weber, 1801 (Coleoptera: Chrysomelidae: Galerucinae). 73729 records from CSIRO, North West Shelf Demersal Marine Resources Study 1980-1997. 76 records from Caracterización Floristica del Páramo Tatamá. 101 records from Planktic foraminifera abundance of Hole 28-265. 76 records from Schulgelände des Gymnasiums Nepomucenum (Coesfeld). 143 records from Toxicity of copper to three Macquarie Island marine gastropods 2013/15. 180 records from (Table 7) Distribution of the large, few-chambered Globigerinelloides species in DSDP Hole 79-545. 3 records from Redescription of Lernaeenicus stromatei Gnanamuthu, 1953 (Copepoda: Siphonostomatoida: Pennellidae) infesting the Black Pomfret Parastromateus niger (Bloch) from Indian waters. 101 records from Benthic foraminifera abundance of Hole 42-372. 1458 records from HUCPE - Herbário da Universidade Católica de Pernambuco. 26 records from Macroinvertebrados de la ciénaga La Honda, Tanguí. 469920 records from Natural England Marine Monitoring surveys. 756 records from Range table from benthic foraminifers in ODP Hole 139-857A. 3397 records from Occurrences portant sur 941 espèces de plantes appartenant à 45 familles de l'herbier du Centre National de Floristique, en Côte d'Ivoire. 148 records from (Table 4) Dinoflagellate cysts from sediment core PS1295-5. 15 records from A new species of the genus Protopolybia Ducke, 1905 (Hymenoptera, Vespidae, Polistinae), with taxonomic contributions to the exigua species-group. 274 records from Taxonomic revision of Agraphydrus Régimbart, 1903 I. China and Taiwan (Coleoptera: Hydrophilidae: Acidocerinae). 10 records from The Pselaphinae (Coleoptera: Staphylinidae) of Madagascar. VI. Description of Ambohitantella banari gen. et sp. n. with notes on Nearticerodes Jeannel, 1954 and Triceratomerus Jeannel, 1960. 122 records from Foraminifera species abundances from tow TT011_10-MOC71. 546 records from Microzooplankton (larger protists and small copepods) abundance measured on concentrated water bottle samples at station PS65/544-6. 6627 records from ATCC Fungi Collection Catalog. 2 records from New Cheilostomata (Bryozoa) species from sublittoral and bathyal zones off the Faroe Islands, with some comments on allied taxa. 2868 records from Tree Diversity and Dynamics of the Forest of Seu Nico (Brazil/MG). 44 records from New records of chalcidid (Hymenoptera: Chalcididae) pupal parasitoids from India. 2581 records from Phytoplankton abundance during G. M. Dannevig cruise GMD90/12. 120 records from Dead benthic foraminifera from surface sediments of the Indian and Pakistan continental margin (Table 1). 10345 records from (Appendix A) Abundances of planktonic foraminifera in mid-Pleistocene sediments of ODP Site 184-1144 in the South China Sea. 242 records from (Table 1) Bottom fauna Metazoa in grab samples from the Namibia shelf in the area of Benguela upwelling. 4387 records from Environment Agency Eiseniella tetraedra Records (England). 103 records from Range table from planktonic foraminifers in ODP Hole 170-1040B. 65 records from Total living benthic foraminifera at station M33/1_MC-25 (EAST), size fraction >30 µm. 10 records from Microzooplankton abundance and biomass at station TT050_7-9. 25 records from Glyptothorax botius (Hamilton, 1822), a valid species of catfish (Teleostei: Sisoridae) from northeast India, with notes on the identity of G. telchitta (Hamilton, 1822).. 183 records from BID-Malawi's-Notodontidae-Biodiversity-Data. 2034 records from Coleoptera Collection. 2 records from Simpsonichthys suzarti sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual fish from the Rio Pardo floodplains, northeastern Brazil.. 1429 records from Kangawalla Bird Sightings. 1 records from Nothrus peltifer. 4 records from Two deep-sea decapod crustaceans collected off eastern Hokkaido, Japan: Sclerocrangon rex n. sp. (Caridea: Crangonidae) and Munidopsis verrilli Benedict, 1902 (Anomura: Munidopsidae). 2 records from A new subspecies of Zamenis hohenackeri (Strauch, 1873) (Serpentes: Colubridae) based on morphological and molecular data. 4031 records from Benthic foraminifera distribution of sediment core GIK17957-2. 41 records from Review of the genus Promalactis Meyrick, 1908 (Lepidoptera: Oecophoridae) III. The trilineata species group, with descriptions of four new species. 1 records from Off the scale: a new species of fishscale gecko (Squamata: Gekkonidae: Geckolepis) with exceptionally large scales. 15691 records from Mollusques dulcicoles de France - Jacques MOUTHON. 606 records from Molluscan specimens from the Astrolabe Reefs (Kadavu, Fiji), 1986-2006. 50 records from Antractic whale observation on a platform of opportunity abroad krill fishing vessel "Dalmor II", April - July 2011.. 621 records from BID-Malawi-Geometridae-Biodiversity-Data. 94 records from A new species of the Liolaemus alticolor - bibronii group (Iguania: Liolaemidae) from East-central Argentina. 360 records from Relative abundance of Neogene nannofossils at ODP Site 138-844 from the eastern equatorial Pacific. 32 records from Foraminifera species abundances from tow TT007_15-MOC23. 190 records from The freshwater shrimp family Euryrhynchidae Holthuis, 1950 (Crustacea: Decapoda: Caridea) revisited, with a taxonomic revision of the genus Euryrhynchus Miers, 1878. 80906 records from Collection Aves (bird skins) SMF. 636 records from Nematode abundance in sediments obtained during RRS Discovery cruise D297. 4054 records from Computarización de la Colección de helmintos parásitos de peces del estado de Tabasco. 46 records from Stable carbon and oxygen isotope record of Cretaceous planktonic foraminifera from DSDP (Table 1). 1 records from Nymph inadvertently described as new species for a fourth time? On the identity of Euscelimena hardi (Tetrigidae: Scelimeninae) with general remarks on the identification of pygmy grasshopper nymphs. 18 records from Rediscovery and redescription of Laelaps lignicola G. & R. Canestrini, a remarkable myrmecophilous mite of the genus Cosmolaelaps Berlese (Acari: Mesostigmata: Laelapidae) from Italy. 262 records from (Fig. 5) Distribution and stable isotope record of foraminifera, and ice-rafted debris of sediment core PS1230-1 (fig 5). 316 records from Planktic foraminifera abundance of Hole 42-375. 2223 records from Données de Lépidoptères de Bruno DAUGET - Dépt de l'ALLIER (03). 17807 records from Condition of rocky reef communities around Tasmania: fish surveys, Australia (1992-1995 and 2006-2007). 96 records from Planktic foraminifera abundance of Hole 32-305. 89 records from BIRDRACE Hasenclevers Erben - NaBu-Bi-BirdRace-Open. 18 records from Range table from dinoflagellates, acritarchs and prasinophytes in ODP Hole 159-960A. 18224 records from TPWD HARC Texas Coastal Fisheries Upper Laguna Madre Gill Net. 64 records from Anfibios y reptiles del páramo de Sumapaz - Proyecto Colombia Bio. 1514 records from Gemeinde Sursee. 2 records from Two new species of Hyalella (Crustacea, Amphipoda, Hyalellidae) from state of Rio Grande do Sul, Southern Brazil. 277 records from Nannofossil abundance of Hole 67-496. 5224 records from Insect specimens of Omogo Mountain Museum. 537 records from Relative abundance of benthic foraminifera in sediment core SO90-137KA. 852 records from OMMAG_Suivi_Dauphins_Les_Saintes. 569 records from Spatial repartition of Antiaris toxicaria Lesch., Ceiba pentandra (L) Gaert, Terminalia superba Engl. & Diels and Triplochyton scleroxylon K. Schum. in Niaouli, Bonou, Pobe forests (South-Benin). 273 records from Freshwater Bullhead Survey Data in Wales. 136 records from Planktic foraminifera abundance of Hole 9-80. 10 records from Revision of the spider crab genus Sargassocarcinus Ward, 1936 (Crustacea: Brachyura: Epialtidae). 149 records from Trockenhang Greinhartsberg Edelfingen. 68939 records from European Invertebrate Survey (EIS-NL) - Orthoptera Observations. 18 records from Locations at sea of adult females of southern elephant seals (Mirounga leonina) from Península Valdés, Chubut, Argentina. 62 records from Tag der Artenvielfalt BUND Kaiserslautern. 1099 records from Caracterización biológica de la ventana de biodiversidad del Complejo Cenagoso de Zapatosa, Municipio de Chimichagua, Cesar, Colombia. 10 records from Microplankton abundance in the euphotic zone of the Cretan Sea at Station JULY-1995-D2. 1 records from Nothrus biciliatus. 1470 records from National Taiwan Museum. 537 records from Données naturalistes de Christophe HERVE. 56 records from (Table 3) Quantitative parameters of the Emiliania huxleyi population along the section from the Pribilofs Islands to the Nunivak Island carried out on 24 and 25 August 2001. 2 records from Arthropoden aus südostalpinen Höhlen.. 456 records from Levantamento de Arbóreas do Parque Nacional do Jaú. 1351 records from (Table T9) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones P5-P7. 19 records from Inventaire National du Patrimoine Naturel : Données sur Tamias sibiricus (Ecureuil de Corée). 471508 records from SER Species-based Surveys. 191 records from Fauna inventories from the intertidal zone in Wimereux, France. 211401 records from River Macrophytes Database. 3 records from A new species of the alpheid shrimp genus Thuylamea Nguyên, 2001 (Crustacea: Decapoda: Caridea) from Yatsushiro Sea, Kyushu, Japan. 800 records from (Table 1) Distribution of larger benthic and planktonic foraminifers in ODP Hole 135-841B. 157063 records from NINA insect database. 8 records from Cirrhigaleus australis n. sp., a new Mandarin dogfish (Squaliformes: Squalidae) from the south-west Pacific.. 17 records from The Neotropical species of Clistopyga (Hymenoptera, Ichneumonidae, Pimplinae). Part II: the C. isayae species group, with the description of seven new species. 240 records from Foraminiferal paleotemperatures (MAT) and relative abundances from core M23414 (GIK23414-9). 275 records from Macromycetes in Portugal Update. 3 records from A new spider species of the genus Sudharmia from Sumatra, Indonesia (Araneae, Liocranidae). 9 records from Visual Plants (144.41.33.158) - Plants from Southern Ecuador; Daniel Piechowski. 40 records from (Supplementary Table 2) Estimates of bottom-water oxygenation at site GeoB11185-1. 3000 records from Fortalecimiento de la Colección de fotocolectas biológicas (CFB): una propuesta del uso de la imagen digital al servicio del conocimiento de la biodiversidad. 101 records from Three new Eustala (Araneae, Araneidae) species from the Galápagos Islands (Ecuador). 100 records from orstom_macassar_corindon_1980. 5295 records from PNR_Alpilles_2017_12_18. 20 records from Description of a new species of the genus Caeneressa from China, with a checklist of the genus (Lepidoptera: Erebidae). 44801 records from Lichen herbarium, NTNU University Museum. 5133 records from (Figure 3) Distribution chart of creatceous planktonic foraminifera of ODP Hole 122-762C. 69 records from Planktic foraminifera abundance of Hole 32-313. 93 records from Höltigbaum. 11 records from First record of ectoparasitic ciliates, of genus Trichodina (Ciliophora: Trichodinidae) parasiting cultured Oranda Gold Fish (Carassius auratus auratus L.) in India. 61 records from A taxonomic revision of the catshark genus Holohalaelurus Fowler 1934 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae), with descriptions of two new species.. 69 records from A new East African genus of spirostreptid millipedes (Diplopoda, Spirostreptida, Spirostreptidae), with notes on their fungal ectoparasite Rickia gigas. 7600 records from (Figure 6) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-550. 245 records from Distribution of planktic foraminifera (250-500 µm) of sediment core GIK17732-1. 1 records from Synthèse de la Répartition des populations de daim en 2013 (réseau Ongulés sauvages ONCFS-FNC-FDC). 2088 records from Actualización de la base de datos de helmintos parásitos de peces de agua dulce de México. 99 records from BIRDRACE TEAM BO-BACHTER. 56 records from Zitadelle Berlin-Spandau (7b). 1 records from Crenicichla ploegi, a new species of pike-cichlid of the C. saxatilis group from the Rio Juruena and upper Rio Paraguai basins in Brazil, with an updated diagnosis and biogeographical comments on the group (Teleostei: Cichlidae). 3224 records from Distribución geográfica de las lagartijas partenogenéticas del género Aspidoscelis en México. 12512 records from ULg_Hexapoda. 6084 records from Ty Canol National Nature Reserve (NNR) Species Inventory. 13621 records from ZFMK Orthopteroidea collection. 175 records from Neißetal. 273 records from Planktic foraminifera abundance of Hole 67-500.
Keywords: GBIF; biodiversity; species occurrences